Systems and methods for depositing phosphor-containing inks
By developing Mn4+ doped phosphor ink composition suitable for miniaturized LED elements, the problem of low application efficiency of phosphor materials in the prior art is solved, and the improvement of high color quality and optical performance is achieved.
Patent Information
- Application Number
- CN202380042989.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-04-26
- Filing Date
- 2023-05-04
- Publication Date
- 2025-02-18
AI Technical Summary
The prior art is difficult to effectively apply phosphor material to miniaturized μm-sized LED elements, limiting the application potential of small LED and micro LED technologies.
An ink composition is developed, comprising a Mn4+ doped phosphor material with a viscosity range of 2000 cP to 30,000 cP, suitable for different printing technologies such as inkjet printing, flexographic printing and screen printing.
It realizes efficient application of phosphor materials on miniaturized LED components, improves color quality and optical performance, and meets the application needs of small LED and micro LED technologies.
Smart Images

Figure CN119487135A_ABST
Abstract
Description
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS
[0002] This application claims priority to U.S. Provisional Patent Application Serial No. 63 / 338,428, entitled “PHOSPHORS, INK FORMULATIONS AND FILMS,” filed on May 4, 2022, U.S. Provisional Patent Application Serial No. 63 / 338,868, entitled “PRINTING, FILMS AND SUBSTRATES,” filed on May 5, 2022, U.S. Provisional Patent Application Serial No. 63 / 453,396, entitled “PHOSPHOR CONVERTED MICROLED ARRAY WITH REFLECTIVE LAYER FOR ATRANSPARENT DISPLAY ARCHITECTURE,” filed on March 20, 2023, and U.S. Provisional Patent Application Serial No. 63 / 498,414, entitled “PHOSPHOR INK PRINTED COLOR FILTER PARTS,” filed on April 26, 2023, which are hereby incorporated by reference in their entirety. Background Art
[0003] The subject matter described herein generally relates to depositing inks containing phosphor materials for lighting and display applications.
[0004] Narrow-band emitting phosphor materials enable high color quality in LED-based lighting and displays. Next-generation displays may incorporate LEDs with 10,000 μm 2 Small LEDs and micro-LEDs with an active area of 100 μm or less are capable of producing light visible to the human eye at very low drive currents. Small LEDs are LEDs with a size of about 100 μm to 0.7 mm. For micro-LEDs, the display can be self-luminous or include a miniaturized backlight and be arranged with individual LEDs smaller than 100 μm.
[0005] New methods of applying phosphor materials to miniaturized μm-sized LED elements need to be developed to realize the full potential of small-LED and micro-LED technology. Coating and printing films of phosphor materials, such as inkjet printing, spin coating or slot die coating, are being developed to prepare LEDs including small-sized LEDs.
[0006] Inkjet printable inks have been prepared using quantum dots. Quantum dot materials have nanoparticle size and strong absorption coefficients. Quantum dots have low quantum efficiency (QE) and poor thermal stability, which significantly limits their practical applications.
[0007] Phosphors have improved properties compared to quantum dot materials. Phosphors for use with small-sized LEDs must have correspondingly small sizes. Printing and coating compositions require stable dispersions, and phosphor materials with common organic solvents can produce sedimentation or phase separation, which is undesirable for subsequent coating and printing processes. In addition, phosphor materials with small particle sizes tend to aggregate when mixed with commonly used solvents, making them unsuitable for ink compositions or formulations. Summary of the invention
[0008] In one embodiment, an ink composition is provided. The ink composition comprises Mn containing Formula 1 4+ The phosphor material of the doped phosphor and at least one binder material or solvent, wherein Mn 4+ The D50 particle size of the doped phosphor is from about 0.5 microns to about 15 microns, and wherein the viscosity of the ink composition is from greater than 2000 cP to about 30,000 cP
[0009] A x [MF y ]:Mn 4+ I
[0010] wherein A is Li, Na, K, Rb, Cs or a combination thereof; M is Si, Ge, Sn, Ti, Zr, Al, Ga, In, Sc, Y, La, Nb, Ta, Bi, Gd or a combination thereof; x is [MF y ]The absolute value of the charge of the ion; and y is 5, 6 or 7.
[0011] In another embodiment, a method for inkjet printing, flexographic printing or microdispensing printing is disclosed. The method includes printing an ink composition, wherein the ink composition includes a low viscosity ink composition, the low viscosity ink composition comprising a Mn containing Formula 1 4+ The phosphor material of the doped phosphor and at least one binder material or solvent, wherein Mn 4+ The D50 particle size of the doped phosphor is from about 0.5 microns to about 5 microns, and wherein the viscosity of the ink composition is from 10 cP to about 1000 cP
[0012] A x [MF y ]:Mn 4+ I
[0013] wherein A is Li, Na, K, Rb, Cs or a combination thereof; M is Si, Ge, Sn, Ti, Zr, Al, Ga, In, Sc, Y, La, Nb, Ta, Bi, Gd or a combination thereof; x is [MF y ]The absolute value of the charge of the ion; and y is 5, 6 or 7.
[0014] In another embodiment, a method for screen printing, direct writing printing, aerosol jet printing, gravure printing, flexographic printing or micro-dispensing printing is disclosed. The method includes printing an ink composition, wherein the ink composition includes a medium viscosity ink composition, the medium viscosity ink composition includes Mn containing Formula 1 4+ The phosphor material of the doped phosphor and at least one binder material or solvent, wherein Mn 4+ The D50 particle size of the doped phosphor is from about 0.5 microns to about 15 microns, and wherein the viscosity of the ink composition is from 1000 cP to about 10,000 cP
[0015] A x [MF y ]:Mn 4+ I
[0016] wherein A is Li, Na, K, Rb, Cs or a combination thereof; M is Si, Ge, Sn, Ti, Zr, Al, Ga, In, Sc, Y, La, Nb, Ta, Bi, Gd or a combination thereof; x is [MF y ]The absolute value of the charge of the ion; and y is 5, 6 or 7.
[0017] In another embodiment, a method for direct writing printing or extrusion is disclosed. The method includes printing or extruding an ink composition, wherein the ink composition includes a high viscosity phosphor-doped ink composition, the high viscosity ink composition includes a Mn containing Formula 1 4+ The phosphor material of the doped phosphor and at least one binder material or solvent, wherein Mn 4+ The D50 particle size of the doped phosphor is from about 0.5 microns to about 15 microns, and wherein the viscosity of the ink composition is from 10,000 cP to about 30,000 cP
[0018] A x [MF y ]:Mn 4+ I
[0019] wherein A is Li, Na, K, Rb, Cs or a combination thereof; M is Si, Ge, Sn, Ti, Zr, Al, Ga, In, Sc, Y, La, Nb, Ta, Bi, Gd or a combination thereof; x is [MF y ]The absolute value of the charge of the ion; and y is 5, 6 or 7.
[0020] In another embodiment, a device is disclosed that includes an LED light source optically coupled and / or radiatively connected to a phosphor composition comprising a Mn containing Formula 14+ The phosphor material of the doped phosphor, wherein Mn 4+ The doped phosphor has a D50 particle size of about 0.5 microns to about 15 microns, and wherein the aspect ratio of the phosphor composition coupled to the LED light source is at least 0.1,
[0021] A x [MF y ]:Mn 4+ I
[0022] wherein A is Li, Na, K, Rb, Cs or a combination thereof; M is Si, Ge, Sn, Ti, Zr, Al, Ga, In, Sc, Y, La, Nb, Ta, Bi, Gd or a combination thereof; x is [MF y ]The absolute value of the charge of the ion; and y is 5, 6 or 7.
[0023] In another embodiment, a color filter component is disclosed. The color filter component comprises a well, a first ink phosphor composition and a second ink phosphor composition, the first ink composition having a high refractive index and the second ink phosphor composition having a low refractive index, wherein the second ink phosphor composition is located near the surface through which the excitation light enters, and the first ink phosphor composition and the second ink phosphor composition comprise a Mn containing Formula 1. 4+ The phosphor material of the doped phosphor and at least one binder material or solvent, wherein Mn 4+ The D50 particle size of the doped phosphor is from about 0.5 microns to about 15 microns, and wherein the viscosity of the ink composition is from about 10,000 cP to about 30,000 cP
[0024] A x [MF y ]:Mn 4+ I
[0025] wherein A is Li, Na, K, Rb, Cs or a combination thereof; M is Si, Ge, Sn, Ti, Zr, Al, Ga, In, Sc, Y, La, Nb, Ta, Bi, Gd or a combination thereof; x is [MF y ]The absolute value of the charge of the ion; and y is 5, 6 or 7.
[0026] In another embodiment, a method includes depositing a first ink composition into a well of a color filter component, and subsequently depositing a second ink composition into the well of the color filter component, wherein the first ink composition has a high refractive index and the second ink composition has a low refractive index, wherein the second ink composition is located near a surface through which excitation light enters, wherein the first ink phosphor composition and the second ink phosphor composition comprise a Mn containing Formula 1 4+The phosphor material of the doped phosphor and at least one binder material or solvent, wherein Mn 4+ The D50 particle size of the doped phosphor is from about 0.5 microns to about 15 microns, and wherein the viscosity of the ink composition is from about 10,000 cP to about 30,000 cP
[0027] A x [MF y ]:Mn 4+ I
[0028] wherein A is Li, Na, K, Rb, Cs or a combination thereof; M is Si, Ge, Sn, Ti, Zr, Al, Ga, In, Sc, Y, La, Nb, Ta, Bi, Gd or a combination thereof; x is [MF y ]The absolute value of the charge of the ion; and y is 5, 6 or 7.
[0029] In another embodiment, a light-emitting array is disclosed. The light-emitting array includes a plurality of micro-LEDs, each micro-LED being encapsulated in a bank structure or a well structure, the bank structure or the well structure being configured to contain an ink composition deposited in the bank structure or the well structure, the phosphor ink composition comprising Mn containing Formula 1 4+ The phosphor material of the doped phosphor and at least one binder material or solvent, Mn 4+ The D50 particle size of the doped phosphor is from about 0.5 microns to about 15 microns, and wherein the viscosity of the ink composition is from 10,000 cP to about 30,000 cP
[0030] A x [MF y ]:Mn 4+ I
[0031] wherein A is Li, Na, K, Rb, Cs or a combination thereof; M is Si, Ge, Sn, Ti, Zr, Al, Ga, In, Sc, Y, La, Nb, Ta, Bi, Gd or a combination thereof; x is [MF y ]The absolute value of the charge of the ion; and y is 5, 6 or 7.
[0032] In another embodiment, a transparent display is disclosed. The transparent display includes a micro-LED array coated with a phosphor composition, wherein the transparency of the transparent display is at least 50%, and the phosphor ink composition includes Mn of Formula 1. 4+ Doped phosphors, where Mn 4+ The doped phosphor has a D50 particle size of about 0.5 microns to about 15 microns, and wherein the aspect ratio of the phosphor composition is at least 0.1,
[0033] Ax [MF y ]:Mn 4+ I
[0034] wherein A is Li, Na, K, Rb, Cs or a combination thereof; M is Si, Ge, Sn, Ti, Zr, Al, Ga, In, Sc, Y, La, Nb, Ta, Bi, Gd or a combination thereof; x is [MF y ]The absolute value of the charge of the ion; and y is 5, 6 or 7. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] These and other features, aspects and advantages of the present disclosure will become better understood when the following detailed description is read with reference to the accompanying drawings, in which like characters refer to like parts throughout the drawings, and in which:
[0036] Figure 1A is a schematic cross-sectional view of a device according to one embodiment of the present disclosure.
[0037] Figure 1B is a schematic cross-sectional view of a device according to an exemplary embodiment.
[0038] Figure 1C is a schematic cross-sectional view of a device according to an exemplary embodiment.
[0039] Figure 1D is a schematic cross-sectional view of a device according to an exemplary embodiment.
[0040] Figure 1E is a schematic cross-sectional view of a device according to an exemplary embodiment.
[0041] Figure 2 is a schematic cross-sectional view of a lighting device according to one embodiment of the present disclosure.
[0042] Figure 3 is a schematic cross-sectional view of a lighting device according to another embodiment of the present disclosure.
[0043] Figure 4 is a cross-sectional side perspective view of a lighting device according to one embodiment of the present disclosure.
[0044] Figure 5A is a schematic perspective view of a surface mount device (SMD) according to one embodiment of the present disclosure.
[0045] Figure 5B is a schematic cross-sectional view of a SMD according to an exemplary embodiment.
[0046] Figure 5C is a schematic cross-sectional view of a device according to an exemplary embodiment.
[0047] Figure 6 is a schematic diagram of a contact stencil printing system according to an embodiment of the present disclosure.
[0048] Figure 7 is a schematic diagram of a screen pitch stencil printing system according to an embodiment of the present disclosure.
[0049] FIG. 8A to FIG. 8D is a schematic diagram of a printed well arrangement according to an embodiment of the present disclosure.
[0050] Fig. 9 is a schematic diagram of a bank arrangement according to an embodiment of the present disclosure.
[0051] Fig.10 is used Figure 6 Diagram of a composition deposited on a substrate by a contact stencil printing system.
[0052] Fig.11 is used Figure 7 Diagram of the screen pitch of the composition deposited on a substrate by the stencil printing system.
[0053] Fig. 12A and Fig. 12B Included are graphs representing the aspect ratios of printed ink composition patterns deposited using screen pitch stencil printing according to embodiments of the present disclosure.
[0054] Fig.13A and Fig. 13B showing a printed ink composition pattern deposited via screen pitch stencil printing, and Fig. 13B is the photoluminescence intensity graph of the pattern.
[0055] Fig.14A and Fig. 14B is a schematic diagram of a high precision pick and place system according to an embodiment of the present disclosure.
[0056] Fig.15 is a dip coating system according to an embodiment of the present disclosure.
[0057] Fig.16A and Fig. 16B 2 are top and side views, respectively, of an example red-green-blue (RGB) pixel according to an embodiment of the present disclosure.
[0058] Fig.17 is a graph comparing red light emission of color filter components having red sub-pixels filled with KSF phosphor including 8 μm depth and 16 μm depth according to an embodiment of the present disclosure.
[0059] Fig.18 Photoluminescence mapping of a blank substrate is shown.
[0060] Fig.19 Photoluminescence mapping of a KSF-filled red sub-pixel is shown.
[0061] Fig. 20 A graph showing the external quantum efficiency (EQE) percentage is shown.
[0062] Fig.21 is a schematic diagram of a hybrid conductive mesh according to an embodiment of the present disclosure.
[0063] Fig. 22 is a contour plot of the color points of an example LED array.
[0064] Unless otherwise indicated, the drawings provided herein are intended to illustrate features of the embodiments of the present disclosure. These features are considered applicable to a variety of systems including one or more embodiments of the present disclosure. Therefore, the drawings are not meant to include all conventional features required for practicing the embodiments disclosed herein that are known to those of ordinary skill in the art. DETAILED DESCRIPTION
[0065] In the following description and claims, reference will be made to a number of terms which will be defined to have the following meanings.
[0066] The singular forms "a", "an" and "the" include plural references unless the context clearly dictates otherwise. As used herein, the term "or" is not meant to be exclusive but means that at least one of the referenced components is present and includes the case in which combinations of the referenced components may be present unless the context clearly dictates otherwise.
[0067] Approximate language, as used throughout the specification and claims, may be applied to modify any quantitative representation that may be permissibly varied without resulting in a change in the basic function to which it is related. Therefore, values modified by one or more terms such as "about," "substantially," and "approximately" are not limited to the precise values specified. In at least some cases, approximate language may correspond to the precision of the instrument used to measure the value. Here and throughout the specification and claims, range limitations may be combined and / or interchanged, and such ranges are identified and include all subranges contained therein unless the context or language indicates otherwise.
[0068] “Optional” or “optionally” means that the subsequently described event or circumstance can or cannot occur, or the subsequently identified material can or cannot be present, and that the description includes instances where the event or circumstance occurs or the material is present and instances where it does not occur or the material is not present and instances where the event or circumstance does not occur.
[0069] The square brackets in the formula indicate that at least one of the elements is present in the phosphor material, and any combination of two or more of them may be present. For example, the formula [Ca, Sr, Ba] 3Mg Si 2 O 8:Eu 2+ ,Mn 2+ Contains at least one of Ca, Sr or Ba, or any combination of two or more of Ca, Sr or Ba. Examples include Ca3MgSi2O8:Eu 2+ .Mn 2+ , Sr3MgSi2O8:Eu 2+ .Mn 2+ or Ba3MgSi2O8:Eu 2+ .Mn 2+ A formula with an activator after a colon ":" indicates that the phosphor material is doped with the activator. A formula showing more than one activator separated by "," after a colon ":" indicates that the phosphor material is doped with any one activator or two activators. For example, the formula [Ca, Sr, Ba] 3MgSi2O8:Eu 2+ ,Mn 2+ Covering [Ca,Sr,Ba]3MgSi2O8:Eu 2+ ,[Ca,Sr,Ba]3MgSi2O8:Mn 2+ or [Ca,Sr,Ba]3MgSi2O8:Eu 2+ and Mn 2+ .
[0070] In one aspect, an ink composition is provided. The ink composition comprises a Mn containing formula 1 4+ The phosphor material of the doped phosphor and at least one binder material or solvent, wherein Mn 4+ The D50 particle size of the doped phosphor is from about 0.5 microns to about 15 microns, and wherein the viscosity of the ink composition is from greater than 2000 cP to about 30,000 cP
[0071] A x [MF y ]:Mn 4+ I
[0072] wherein A is Li, Na, K, Rb, Cs or a combination thereof; M is Si, Ge, Sn, Ti, Zr, Al, Ga, In, Sc, Y, La, Nb, Ta, Bi, Gd or a combination thereof; x is [MF y ]The absolute value of the charge of the ion; and y is 5, 6 or 7.
[0073] The ink composition can be customized for a specific printing application. For example, the ink composition can be customized for any of the following printing applications: inkjet printing, flexographic printing, or microdispensing printing, screen printing, direct writing printing, aerosol jet printing, gravure printing, and linking. Additionally or alternatively, the ink composition can be customized for extrusion. For example, a low viscosity ink composition can be customized for inkjet printing, flexographic printing, and / or microdispensing printing; a medium viscosity ink can be customized for screen printing, direct writing printing, aerosol jet printing, gravure printing, flexographic printing, and / or microdispensing printing; and a high viscosity ink can be customized for high viscosity screen printing, direct writing printing, and / or extrusion.
[0074] The ink composition comprises phosphor materials. The type, amount and size of the phosphors are determined by the optical application, in particular the color point and optical density.
[0075] The phosphor material may be present in the ink composition at about 5% to about 70% by weight. In another embodiment, the phosphor material is present at about 30% to about 60% by weight. In another embodiment, the phosphor material is present at about 10% to about 50% by weight. The weight percent of the phosphor material is based on the total weight of the ink composition.
[0076] Mn of Formula I 4+ Doped phosphors are complex fluoride materials or coordination compounds containing at least one coordination center surrounded by fluoride ions acting as ligands and, if necessary, charge compensated by counter ions. 4+ In the example, the coordination center is Si and the counter ion is K. The activator ion (Mn 4+ ) also acts as a coordination center, replacing a portion of the host lattice center, such as Si. The host lattice (including the counterions) can further modify the excitation and emission characteristics of the activator ion.
[0077] In certain embodiments, the coordination center of the phosphor (i.e., M in Formula I) is Si, Ge, Sn, Ti, Zr, Al, Ga, In, Sc, Y, La, Nb, Ta, Bi, Gd, or a combination thereof. More specifically, the coordination center can be Si, Ge, Ti, or a combination thereof. The counterion or A in Formula I can be Li, Na, K, Rb, Cs, or a combination thereof, more specifically K or Na. Examples of phosphors of Formula I include K2[SiF6]:Mn 4+ 、K2[TiF6]:Mn 4+ 、K2[SnF6]:Mn 4+ 、Cs2[TiF6]:Mn 4+ 、K2[GeF6]Mn 4+ 、Rb2[TiF6]Mn 4+、Cs2[SiF6]:Mn 4+ 、Rb2[SiF6]:Mn 4+ 、Na2[SiF6]:Mn 4+ 、Na2[TiF6]:Mn 4+ 、Na2[ZrF6]:Mn 4+ 、K3[ZrF7]:Mn 4+ 、K3[BiF6]、K3[YF6]:Mn 4+ 、K3[LaF6]:Mn 4+ 、K3[GdF6]:Mn 4+ 、K3[NbF7]:Mn 4+ 、K3[TaF7]:Mn 4+ In a specific embodiment, the phosphor of formula I is K2SiF6:Mn 4+ (PFS) or Na2[SiF6]:Mn 4+ (NSF).
[0078] Mn doping 4+ The amount of activator Mn in the doped phosphor (referred to as Mn%) improves color conversion. Increasing the amount of Mn% incorporation improves color conversion by increasing the intensity of red emission, maximizing absorption of excitation blue light and reducing the amount of unconverted blue light or blue light penetration from blue LEDs.
[0079] In one embodiment, the red emitting Mn 4+ The doped phosphor has a Mn loading or Mn% of at least 1 wt%. In another embodiment, the red emitting phosphor has a Mn loading of at least 1.5 wt%. In another embodiment, the red emitting phosphor has a Mn loading of at least 2 wt%. In another embodiment, the red emitting phosphor has a Mn loading of at least 3 wt%. In another embodiment, the Mn% is greater than 3.0 wt%. In another embodiment, the Mn content in the red emitting phosphor is about 1 wt% to about 4 wt%. In another embodiment, the red emitting phosphor has a Mn% of about 2 wt% to about 5 wt%.
[0080] In one embodiment, Mn 4+ The doped phosphor can be manganese-doped potassium fluorosilicate, such as K2SiF6:Mn 4+ (PFS). PFS has narrow-band emission with multiple peaks with an average full width at half maximum (FWHM) of less than 4 nm. In another embodiment, the red emitting phosphor may be Na2SiF6:Mn 4+ (NFS).
[0081] In one embodiment, the Mn may be further processed4+ Doping the phosphor, such as by annealing, washing treatment, firing, or any combination of these treatments. Mn 4+ Post-processing of doped phosphors is described in U.S. Pat. No. 8,906,724, U.S. Pat. No. 8,252,613, U.S. Pat. No. 9,698,314, U.S. Publication No. 2016 / 0244663, U.S. Publication No. 2018 / 0163126, and U.S. Publication No. 2020 / 0369956. The entire contents of each of which are incorporated herein by reference. In one embodiment, Mn 4+ The doped phosphor may be annealed, treated with multiple washing processes and fired.
[0082] In order to improve reliability, Mn 4+ The doped phosphor may be at least partially coated with a surface coating to enhance the stability and resistance to aggregation of the phosphor particles by modifying the surface of the particles and increasing the zeta potential of the particles. In one embodiment, the surface coating may be a metal fluoride, silicon dioxide, or an organic coating. In one embodiment, the phosphor may be a fluoride-based material composed of Mn 4+ The red emitting phosphor of the phosphor activated composite fluoride material is at least partially coated with a metal fluoride, which increases the positive zeta potential and reduces agglomeration. In one embodiment, the metal fluoride coating comprises MgF2, CaF2, SrF2, BaF2, AgF, ZnF2, AlF3, or a combination thereof. In another embodiment, the amount of the metal fluoride coating is from about 0.1 wt % to about 10 wt %. In another embodiment, the metal fluoride coating is present in an amount of from about 0.1 wt % to about 5 wt %. In another embodiment, the metal fluoride coating is present in an amount of from about 0.3 wt % to about 3 wt %. As described in WO 2018 / 093832, U.S. Publication No. 2018 / 0163126 and U.S. Publication No. 2020 / 0369956, a composite fluoride material based on Mn is prepared. 4+ Activated composite fluoride materials, metal fluoride coated red emitting phosphors, each of which is incorporated herein by reference in its entirety.
[0083] The phosphor material may include additional phosphors, such as yttrium aluminum garnet phosphor (YAG). The powder ratio (YAG:PFS) may be adjusted to achieve a desired color point. The phosphor material may include additional phosphors, such as rare earth garnet phosphors. Rare earth elements include: Sc, Y, La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb and Lu. In one embodiment, the rare earth garnet phosphor is yttrium aluminum garnet phosphor (YAG). The ratio of the rare earth garnet phosphor to the Mn4+ doped phosphor may be adjusted to achieve a desired color point.
[0084] The ink composition comprises at least one binder material or at least one solvent. In some embodiments, the ink composition comprises a binder material and a solvent.
[0085] The ink composition may include a binder material to further optimize the ink properties. A variety of binders and resin systems with different chemistries and viscosities may be used.
[0086] In one embodiment, the binder matrix comprises a cross-linked polymer. In another embodiment, the binder material comprises a curable material, such as a photocurable or UV curable material or a heat curable or thermosetting binder material or a combination. The heat curable or thermosetting binder material will polymerize or cross-link and form a cured resin binder matrix. Exemplary thermosetting and UV binder materials include epoxies, acrylates, methacrylates, vinyl esters, and siloxanes. Examples of suitable commercial resin systems include, but are not limited to, Pixelligent UVG curable ink base, optical adhesive (Norland 68T), Pixelligent PixJet SFZ-1 with 40 wt % ZrO2 in an acrylic formulation.
[0087] In one embodiment, the binder material may be present in an amount of up to about 75 % by weight. In another embodiment, the binder may be present in an amount of up to about 70 % by weight. In another embodiment, the binder may be present in an amount of about 5 % by weight to about 75 % by weight. In another embodiment, the binder is present in an amount of about 10 % by weight to about 70 % by weight. In another embodiment, the binder is present in an amount of about 20 % by weight to about 50 % by weight. The % by weight is based on the gross weight of the ink composition.
[0088] In another embodiment, the ink composition comprises a first polymerization initiator and a second polymerization initiator for a 2-step curing process, wherein the first curing step in the photoinitiated polymerization process is initiated by a radiation wavelength of less than 400 nm (UV curing). The first polymerization initiator has a higher decomposition rate than the second polymerization initiator. The second curing process is free of UV radiation, wherein the second polymerization initiator has a higher decomposition rate than the first polymerization initiator. The post-curing phosphor treatment concentration increases by 5%, preferably 10%, and the printed material volume decreases (shrinks) by <20%, preferably <15%. The total printed volume does not exceed 20 volume % shrinkage. The ink composition may include a solvent. The amount of solvent, solvent polarity, and solvent vapor pressure may contribute to the preparation of a stable ink that meets the viscosity, wettability, and optical density standards of the ink composition. The solvent may be present in an amount that effectively dissolves the phosphor material and any binder material and adjusts the ink composition to the desired viscosity. In one embodiment, the solvent may be present in about 5% to about 95% by weight. In another embodiment, the solvent may be present in about 10% to about 75% by weight. In another embodiment, the solvent is present in about 20% to about 50% by weight. The weight percent of solvent is based on the weight of the ink composition.
[0089] Several solvent systems can be used to formulate phosphor particles in inks that have proven utility in the printing industry. Suitable solvents have boiling points and polarities that match the desired printing application and do not interact adversely with the binder materials or phosphors used.
[0090] The solvent may be polar or non-polar. Examples of solvents include, but are not limited to, acetone, glycol ethers such as diethylene glycol methyl ether, propylene methyl acrylates such as propylene glycol dimethacrylate, cyclic aromatic solvents such as toluene, xylene and anisole, aliphatic solvents such as hexane and tetradecane, alcohols such as ethanol, isopropanol and octanol, glycols such as ethylene glycol and propylene glycol, terpineol, acetates such as butyl acetate, propylene glycol methyl ether acetate (PGMEA), N-methylpyrrolidone (NMP), dimethyl sulfoxide (DMSO), dimethylformamide (DMF), diethylene glycol methyl ether (DGME) and ethyl 2-(2-butoxyethoxy)acetate (BEA).
[0091] Co-solvents and solvent mixtures can also be used to improve fluid, printing process and film forming characteristics. A mixture of solvents can consist of any two or more of the solvents listed above, or can consist of adding a small amount of a common organic solvent to one of the above solvents.
[0092] The ink composition comprises a phosphor material having a D50 particle size in the range of about 0.5 to about 15 microns. In order to prepare the ink composition, for printing and for forming a film, the particle size needs to be small. In another embodiment, the phosphor material comprises a D50 particle size in the range of about 0.5 microns to about 10 microns. In another embodiment, the D50 particle size is in the range of about 0.5 microns to about 5 microns.
[0093] D50 (also expressed as D 50 ) is defined as the median particle size of the volume distribution. D90 or D 90 It is the particle size of the volume distribution that is larger than 90% of the particles in the distribution. D10 or D 10 is the particle size of the volume distribution that is greater than the size of 10% of the particles in the distribution. The particle size of the phosphor can be conveniently measured by laser diffraction or optical microscopy methods, and commercially available software can generate the particle size distribution and span. The span is a measure of the width of the particle size distribution curve of a granular material or powder, and is defined according to the following equation:
[0094]
[0095] Where D 90 , D 10 and D 50 As defined above. For phosphor particles, the span of the particle size distribution is not necessarily limited, and in some embodiments may be ≤ 1.0.
[0096] The viscosity of the ink composition is from about 10 cP to about 30,000 cP. In another embodiment, the viscosity is from about 1000 cP to about 30,000 cP.
[0097] In some embodiments, the ink composition is a low viscosity ink composition. The low viscosity ink composition includes a viscosity in the range of about 10 cP to about 1000 cP. In another embodiment, the viscosity of the low viscosity ink composition is about 10 cP to less than 1000 cP. Particles can settle out of the low viscosity ink composition more easily, so it is desirable to include a phosphor material with a very small particle size. The low viscosity ink composition can be used for printing applications, such as bank structures or well structures.
[0098] In one embodiment, the ink composition is a medium viscosity ink composition. The medium viscosity ink composition includes a viscosity in the range of about 1000 cP to about 10,000 cP. In another embodiment, the viscosity is in the range of greater than 1000 cP to less than 10,000 cP.
[0099] In one embodiment, the ink composition is a high viscosity ink composition. The high viscosity ink composition includes a viscosity in the range of about 10,000 cP to about 30,000 cP. In another embodiment, the viscosity is in the range of greater than 10,000 cP to about 30,000 cP.
[0100] The viscosity range is for the starting viscosity range in the ink composition.
[0101] Additional additives may be added to the ink composition to further tailor ink properties or film properties such as adhesion or cohesion, light scattering, evaporation rate, stability, shelf life, and the like.
[0102] In one embodiment, the ink composition includes a scattering aid, such as ZrO2 nanoparticles. Examples of scattering particles include, but are not limited to, titanium dioxide, aluminum oxide (Al2O3), zirconium oxide, indium tin oxide, cerium oxide, tantalum oxide, zinc oxide, magnesium fluoride (MgF2), calcium fluoride (CaF2), strontium fluoride (SrF2), barium fluoride (BaF2), silver fluoride (AgF), aluminum fluoride (AlF3), or combinations thereof. In other embodiments, additional additives improve film quality, such as pentaerythritol tetrakis (3-mercaptopropionate) from Bruno Bock (BB PTh).
[0103] The additive may be added to the ink composition in an amount of about 5 wt % to about 20 wt % based on the weight of the ink composition.
[0104] External heating may be used to improve the flow of the ink composition, however, it should be noted that temperatures exceeding 65°C for extended periods of time may result in premature curing.
[0105] The ink sets were prepared using a solvent-based mixing and removal method.
[0106] The phosphor and solvent or binder material are mixed until the phosphor is dispersed in the solvent and the solvent is partially removed. In some embodiments, the solvent is optional. Typically, the base ink, additives, and a small amount of solvent are mixed together, and then the phosphor material is added in 2-4 increments, mixing between additions. Additional solvent may be required to achieve good dispersion and the desired viscosity for coating.
[0107] When more than one phosphor is present, such as YAG, the second phosphor may be added first, followed by Mn in about 2 g increments. 4+ Phosphor. In one embodiment, the solution is vortexed between each powder addition. For example, the solution can be vortexed for 1 minute after each sampling. In another embodiment, the mixture can be subjected to horn sonication.
[0108] Once the particles are properly dispersed and homogenized, the solvent is partially removed. This process allows for the incorporation of high levels of particles and enables the end user to control viscosity by retaining the amount of solvent in the final formulation.
[0109] In one embodiment, the suspension is subjected to rotary evaporation until the desired amount of solvent is removed.
[0110] The ink solution can be cured after it is applied to the printing techniques described herein. The ink solution can also be coated onto a substrate or formed into a film. In one embodiment, the ink composition is subjected to a suitable temperature for thermal curing or a suitable radiation wavelength for UV curing, such as less than 400 nm.
[0111] In one embodiment, a 2-step curing using UV and thermal curing is applied to the ink composition. The system contains both photosensitive groups and thermal sensitive groups. The first curing process uses UV curing to soft cure the material in place. The wavelength of polymerization initiation is less than 400nm (classified as UV curing). The second curing step is thermal curing, which uses heat to initiate the remainder of the polymerization reaction. The second curing step acts as a bonding or complete curing mechanism. In the film, the second step can reduce the volume of the deposited film by shrinking.
[0112] The advantage of a 2-step curing method for curing films is that it can adjust the degree and point of shrinkage of the deposited film in the process. Depending on the amount of each polymerization initiator, the concentration of the PFS can be tailored by changing the film densification mechanism. UV-only curing systems rely on UV radiation contacting every surface, and curing of shadows or deep areas cannot be assumed. Thermal curing alone is generally not rapid, and therefore "slumping" or separation / skinning may occur in the deposited ink. Using UV curing for a "soft cure" followed by thermal curing for a "full cure", the shape or film can be envisioned.
[0113] A 2 step cure method can also be used to form 1 feature on top of another cured feature via UV cure, followed by thermal cure to further "bond" the two layers together.
[0114] The phosphor material may include one or more other luminescent materials. Additional luminescent materials, such as blue, yellow, red, orange or other colored phosphors, may be used in the phosphor material to tailor the white color of the resulting light and produce a specific spectral power distribution.
[0115] Phosphors suitable for phosphor materials include but are not limited to: ((Sr 1-z [Ca,Ba,Mg,Zn] z ) 1-(x+w) [Li,Na,K,Rb] w Ce x )3(Al 1-y Siy )O 4+y+3(x-w) F 1-y-3(x-w) , 0 < x ≤ 0.10, 0 ≤ y ≤ 0.5, 0 ≤ z ≤ 0.5, 0 ≤ w ≤ x; [Ca,Ce]3Sc2Si3O 12 (CaSiG); [Sr,Ca,Ba]3Al 1-x Si x O 4+x F 1-x :Ce 3+ (SASOF)); [Ba,Sr,Ca]5(PO4)3[Cl,F,Br,OH]:Eu 2+ ,Mn 2+ ; [Ba,Sr,Ca]BPO5:Eu 2+ ,Mn 2+ ; [Sr,Ca] 10 (PO4)6*vB2O3:Eu 2+ (wherein 0 < v ≤ 1); Sr2Si3O8*2SrCl2:Eu 2+ ; [Ca,Sr,Ba]3MgSi2O8:Eu 2+ ,Mn 2+ ; BaAl8O 13 :Eu 2+ ; 2SrO*0.84P2O5*0.16B2O3:Eu 2+ ; [Ba,Sr,Ca]MgAl 10 O 17 :Eu 2+ ,Mn 2+ ; [Ba,Sr,Ca]Al2O4:Eu 2+ ; [Y,Gd,Lu,Sc,La]BO3:Ce 3+ ,Tb 3+ ; ZnS:Cu + ,Cl - ; ZnS:Cu + ,Al 3+ ; ZnS:Ag + ,Cl - ; ZnS:Ag + ,Al 3+ ; [Ba,Sr,Ca]2Si 1- n O 4-2n :Eu 2+ (wherein 0 ≤ n ≤ 0.2); [Ba,Sr,Ca]2[Mg,Zn]Si2O7:Eu 2+ ; [Sr,Ca,Ba][Al,Ga,In]2S4:Eu 2+; [Y, Gd, Tb, La, Sm, Pr, Lu]3[Al, Ga] 5-a O 12-3 / 2a :Ce 3+ (where 0 ≤ a ≤ 0.5); [Ca, Sr]8[Mg, Zn](SiO4)4Cl2:Eu 2+ ,Mn 2+ ; Na2Gd2B2O7:Ce 3+ ,Tb 3+ ; [Sr, Ca, Ba, Mg, Zn]2P2O7:Eu 2+ ,Mn 2+ ; [Gd, Y, Lu, La]2O3:Eu 3+ ,Bi 3+ ; [Gd, Y, Lu, La]2O2S:Eu 3+ ,Bi 3+ ; [Gd, Y, Lu, La]VO4:Eu 3+ ,Bi 3+ ; [Ca, Sr, Mg]S:Eu 2+ ,Ce 3+ ; SrY2S4:Eu 2+ ; CaLa2S4:Ce 3+ ; [Ba, Sr, Ca]MgP2O7:Eu 2+ ,Mn 2+ ; [Y, Lu]2WO6:Eu 3+ ,Mo 6+ ; [Ba, Sr, Ca] b Si g N m :Eu 2+ (where 2b + 4g = 3m); Ca3(SiO4)Cl2:Eu 2+ ; [Lu, Sc, Y, Tb] 2-u-v Ce v Ca 1+ u Li w Mg 2-w P w [Si, Ge] 3-w O 12-u / 2 (where 0.5 ≤ u ≤ 1, 0 < v ≤ 0.1 and 0 ≤ w ≤ 0.2); [Y, Lu, Gd] 2-m [Y, Lu, Gd]Ca m Si4N 6+m C 1-m :Ce 3+ , (where 0 ≤ m ≤ 0.5); [Lu, Ca, Li, Mg, Y], doped with Eu 2+ and / or Ce3+ α-SiAlON; Sr(LiAl3N4):Eu 2+ ,[Ca,Sr,Ba]SiO2N2:Eu 2+ ,Ce 3+ ; beta-SiAlON:Eu 2+ ;3.5MgO*0.5MgF2*GeO2:Mn 4+ ;Ca 1-c-f Ce c Eu f Al 1+c Si 1-c N 3, (where 0≤c≤0.2, 0≤f≤0.2); Ca 1-h- r Ce h Eu r Al 1-h (Mg, Zn) h S N 3, (where 0≤h≤0.2, 0≤r≤0.2); Ca 1-2s-t Ce s [Li,Na] s Eu t AlSiN 3, (where 0≤s≤0.2, 0≤t≤0.2, s+t>0); [Sr,Ca]AlSiN3: and Eu 2+ ,Ce 3+ ,Li2CaSiO4:Eu 2+ .
[0116] In a particular embodiment, the additional phosphor includes: [Y, Gd, Lu, Tb]3[Al, Ga]5O 12 :Ce 3+ 、β-SiAlON:Eu 2+ 、[Sr,Ca,Ba][Ga,Al]2S4:Eu 2+ 、[Li,Ca]α-SiAlON:Eu 2+ 、[Ba,Sr,Ca]2Si5N8:Eu 2+ 、[Ca,Sr]AlSiN3:Eu 2+ 、[Ba,Sr,Ca]LiAl3N4:Eu 2+ 、[Sr,Ca,Mg]S:Eu 2+ and [Ba,Sr,Ca]2Si2O4:Eu 2+ .
[0117] The phosphor material may include at least one green emitting phosphor. The green emitting phosphor may include any suitable green emitting phosphor, including uranium phosphors. In one embodiment, the green emitting uranium phosphor includes but is not limited to Ba3(PO4)2(UO2)2P2O7, Ba3(PO4)2(UO2)2V2O7, gammaγ-Ba2UO2(PO4)2, BaMgUO2(PO4)2, BaZnUO2(PO4)2, Na2UO2P2O7, K2UO2P2O7, Rb2UO2P2O7, Cs2UO2P2O7, K4UO2(PO4) 2、 K4UO2(VO4)2 or NaUO2P3O9, as described in U.S. Patent No. 11,254,864, which is incorporated herein.
[0118] Other additional luminescent materials suitable for use in the ink composition may include electroluminescent polymers such as polyfluorenes, preferably poly(9,9-dioctylfluorene) and copolymers thereof, such as poly(9,9′-dioctylfluorene-co-bis-N,N′-(4-butylphenyl)diphenylamine) (F8-TFB), poly(vinylcarbazole) and polyphenylenevinylene and derivatives thereof. In addition, the luminescent layer may include a blue, yellow, orange, green or red phosphorescent dye or metal complex, quantum dot material or a combination thereof. Materials suitable for use as phosphorescent dyes include, but are not limited to, tris(1-phenylisoquinoline)iridium(III) (red dye), tris(2-phenylpyridine)iridium(green dye) and bis(2-(4,6-difluorophenyl)pyridine-N,C2)iridium(III) (blue dye). Fluorescent and phosphorescent metal complexes commercially available from ADS (American Dyes Source, Inc.) may also be used. ADS green dyes include ADS060GE, ADS061GE, ADS063GE, and ADS066GE, ADS078GE, and ADS090GE. ADS blue dyes include ADS064BE, ADS065BE, and ADS070BE. ADS red dyes include ADS067RE, ADS068RE, ADS069RE, ADS075RE, ADS076RE, ADS067RE, and ADS077RE.
[0119] Exemplary QD materials include, but are not limited to, Group II-IV compound semiconductors such as CdS, CdSe, CdS / ZnS, CdSe / ZnS or CdSe / CdS / ZnS, Group II-VI such as CdTe, ZnSe, ZnTe, ZnS, HgTe, HgS, HgSe, CdSeTe, CdSTe, ZnSeS, ZnSeTe, ZnSTe, HgSeS, HgSeTe, HgSTe, CdZnS, CdZnSe, CdZnTe, CdHgS, CdHgSe, CdHgTe, HgZnS, HgZnSe, HgZnTe, CdZnSeS, CdZnSeTe, CdZnSTe, CdHgSeS, CdHgSeTe, CdHgSTe, HgZnSeS, HgZnSeTe, HgZnSTe, III-V or IV-VI compound semiconductors such as Ga N, GaP, GaNP, GaNAs, GaPAs, GaAs, GaAlNP, GaAlNAs, GaAlPAs, GaInNP, GaInNAs, GaInPAs, AlN, AlNP, AlNAs, AlP, AlPAs, AlAs, InN, InNP, InP, InNAs, InPAs, InAS, InAlNP, InAlNAs, InAlPAs, PbS / ZnS or PbSe / ZnS, Group IV such as Si, Ge, SiC and SiGe, chalcopyrite-type compounds, including but not limited to CuInS2, CuInSe2, CuGaS2, CuGaSe2, AgInS2, AgInSe2, AgGaS2, AgGaSe2 or perovskite QDs having the formula ABX3, wherein A is cesium, methylammonium or methylammonium, B is lead or tin, and C is chloride, bromide or iodide. The quantum dot material may include a core-shell nanostructure having an Ag-In-Ga-S (AIGS) core and an Ag-Ga-S (AGS) shell.
[0120] In one embodiment, the perovskite quantum dot can be CsPbX3, wherein X is Cl, Br, I or a combination thereof. The average size of the QD material can be in the range of about 2nm to about 20nm. The surface of the QD particles can be further modified with ligands such as amine ligands, phosphine ligands, phospholipids and polyvinyl pyridine. In one aspect, the red phosphor can be a quantum dot material.
[0121] All semiconductor quantum dots may also have an appropriate shell or coating for passivation and / or environmental protection. The QD material may be a core / shell QD, comprising a core, at least one shell coated on the core, and an outer coating comprising one or more ligands, preferably organic polymer ligands. Exemplary materials for preparing core-shell QDs include, but are not limited to, Si, Ge, Sn, Se, Te, B, C (including diamond), P, Co, Au, BN, BP, BAs, AlN, AlP, AlAs, AlSb, GaN, GaP, GaAs, GaSb, InN, InP, InAs, InSb, AlN, AlP, AlAs, AlSb, GaN, GaP, GaAs, GaSb, ZnO, ZnS, ZnSe, ZnTe, CdS, CdSe , CdSeZn, CdTe, HgS, HgSe, HgTe, BeS, BeSe, BeTe, MgS, MgSe, MnS, MnSe, GeS, GeSe, GeTe, SnS, SnSe, SnTe, PbO, PbS, PbSe, PbTe, CuF, CuCl, CuBr, CuI, Si3N4, Ge3N4, Al2O3, [Al, Ga, In]2[S, Se, Te]3, and suitable combinations of two or more such materials. Exemplary core-shell luminescent nanocrystals include, but are not limited to, CdSe / ZnS, CdSe / CdS, CdSe / CdS / ZnS, CdSeZn / CdS / ZnS, CdSeZn / ZnS, InP / ZnS, PbSe / PbS, PbSe / PbS, CdTe / CdS, and CdTe / ZnS.
[0122] The ratio of each of the individual phosphors and other luminescent materials in the ink composition can vary depending on the characteristics of the desired light output. The relative proportions of the individual phosphors and other luminescent materials in various ink compositions can be adjusted so that when their emissions are blended and used in a device such as a lighting fixture, visible light of predetermined x and y values is produced on the CIE chromaticity diagram.
[0123] In one embodiment, the film can be prepared from the ink composition. The film can be deposited on a substrate such as a glass substrate. The film can be deposited on an LED, such as a mini-LED or micro-LED, such as by coating, using a scraper or by printing. In one embodiment, the film is prepared by coating the ink composition on a glass substrate with a scraper. The solvent can be removed and the film cured, such as by UV light or thermal curing.
[0124] Additional processes for preparing phosphor compositions that can be used with the systems and methods described herein are described in PCT application number [insert application number], entitled [insert title], filed on May 4, 2023, which is incorporated herein by reference in its entirety.
[0125] In one embodiment, the lighting device comprises the device. In another embodiment, the backlight device comprises the device. In another embodiment, the display comprises the device. In another embodiment, the device is a self-emissive display and does not include a liquid crystal display (LCD). In one embodiment, the display is a micro-LED display, such as a phosphor-converted micro-LED display.
[0126] An apparatus according to the present disclosure includes an LED light source radiatively connected and / or optically coupled to a phosphor composition. Figures 1A to 1E An apparatus 10 is shown according to various embodiments of the present disclosure. Figure 1A , the device 10 includes an LED light source 12 and a phosphor composition 14. The LED light source 12 can be a UV or blue emitting LED. In some embodiments, the LED light source 12 generates blue light with a wavelength in the range of about 380nm to about 460nm. In the device 10, the phosphor composition 14 is radiation coupled and / or optically coupled to the LED light source 12. Radiative connection or coupling or optical coupling means that the radiation from the LED light source 12 can excite the phosphor composition 14, and the phosphor composition 14 can emit light in response to the excitation of the radiation. The phosphor composition 14 can be disposed on a component or portion of the LED light source 12, or at a certain distance away from the LED light source 12. In some embodiments, the device can be a backlight unit for display applications. In other embodiments, the LED light source 12 is a micro-LED, and the device is used for a self-emitting display. Figure 1B An exemplary embodiment is shown in which the phosphor composition 14 is disposed on the LED light source 12. The LED light source 12 is disposed on a reflective layer 16. The reflective layer 16 reflects light from the LED light source 12 toward the LED light source and the phosphor composition 14. The reflective layer 16 can be any material suitable for reflecting light. In one embodiment, the reflective layer 16 can be a metal layer, such as aluminum, silver, a silver alloy, or an aluminum alloy. Figure 1C An exemplary embodiment is shown in which the phosphor composition 14 is disposed on the LED light source 12. An encapsulant or barrier layer 18 is disposed on the phosphor composition 14. The encapsulant or barrier layer 18 can be a low temperature glass, or a polymer or resin known in the art, such as epoxy, silicone, epoxy-silicone, acrylate, or a combination thereof. The encapsulant or barrier layer 18 should be transparent to allow light to pass through these elements. Figure 1D An exemplary embodiment is shown in which LED light sources 14 are depicted as an array of LED light sources 12. In some embodiments, LED light sources 12 are small LEDs or micro-LEDs. Figure 1E An exemplary embodiment is shown in which the phosphor composition 14 is located remote from the LED light sources 12 , which is depicted as an array of LED light sources 12 .
[0127] The general discussion of the example LED light sources discussed herein is directed to light sources based on inorganic LEDs. The most popular white LEDs are based on GaInN chips that emit blue or UV. In addition, for inorganic LED light sources, the term LED light source is intended to cover all LED light sources, such as semiconductor laser diodes (LDs), organic light emitting diodes (OLEDs), or a mix of LEDs and LDs. The LED light source can be a small LED or micro-LED, which can be used for self-emitting displays. In addition, it should be understood that, unless otherwise stated, the LED light source can be replaced, supplemented or increased by another radiation source, and any reference to semiconductors, semiconductor LEDs, or LED chips represents only any appropriate radiation source, including but not limited to LDs and OLEDs.
[0128] The phosphor composition 14 can be present in any form, such as a powder, a glass, or a composite, for example a phosphor-polymer composite or a phosphor-glass composite. In addition, the phosphor composition 14 can be used as a layer, a sheet, a film, a strip, dispersed particles, or a combination thereof. In some embodiments, the phosphor composition 14 includes a uranium-based phosphor material in the form of a glass. In some of these embodiments, the device 10 may include the phosphor composition 14 in the form of a phosphor wheel (not shown). The phosphor wheel may include a phosphor composition embedded in a glass. Phosphor wheels and related devices are described in WO 2017 / 196779.
[0129] The phosphor composition is optically coupled or radiatively connected to an LED light source. In one embodiment, a white light blend can be obtained by mixing a red phosphor material and a green phosphor material with an LED light source, such as a blue or UV LED.
[0130] Figure 2 A lighting device or lamp 20 according to some embodiments is shown. In one embodiment, the lighting device 20 can be a backlight device. The lighting device 20 includes an LED chip 22 and leads 24 electrically connected to the LED chip 22. The leads 24 can include thin wires supported by a thicker lead frame 26, or the leads 24 can include self-supporting electrodes and the lead frame can be omitted. The leads 24 provide current to the LED chip 22, causing it to emit radiation.
[0131] The phosphor composition layer 30 is disposed on the surface of the LED chip 22. The phosphor layer 30 can be disposed by any suitable method, for example, using a slurry or ink composition prepared by mixing the phosphor composition and a binder material or solvent (as discussed above). In one such method, a silicone slurry in which the phosphor composition particles are randomly suspended or evenly dispersed is placed around the LED chip 22. This method is only an example of possible locations of the phosphor layer 30 and the LED chip 22. By coating and drying the slurry on the LED chip 22, the phosphor layer 30 can be coated on the light emitting surface of the LED chip 22 or directly on the light emitting surface. The light emitted by the LED chip 22 is mixed with the light emitted by the phosphor composition to produce the desired emission.
[0132] Continue to refer Figure 3 , the LED chip 22 can be enclosed in a housing 28. The housing 28 can be formed of, for example, glass or plastic. The LED chip 22 can be enclosed by a sealant material 32. The sealant material 32 can be a low temperature glass, or a polymer or resin known in the art, such as epoxy, silicone, epoxy-silicone, acrylate, or a combination thereof. In an alternative embodiment, the lighting device 20 can include only the sealant material 32 without the housing 28. Both the housing 28 and the sealant material 32 should be transparent to allow light to pass through these elements.
[0133] In such Figure 3 In some embodiments shown, the phosphor composition 33 is dispersed within the encapsulant material 32, rather than as Figure 4 The encapsulant material 32 is shown formed directly on the LED chip 22. The phosphor composition 33 may be dispersed within a portion of the encapsulant material 32 or dispersed over the entire volume of the encapsulant material 32. The blue light or UV light emitted by the LED chip 22 is mixed with the light emitted by the phosphor composition 33, and the mixed light is transmitted from the lighting device 20.
[0134] In yet another embodiment, the phosphor composition layer 34 is applied to the surface of the housing 28 rather than being formed on the LED chip 22, such as Figure 4 As shown, the phosphor layer 34 is coated on the inner surface 29 of the housing 28, but if desired, the phosphor layer 34 can be coated on the outer surface of the housing 28. The phosphor layer 34 can be coated on the entire surface of the housing 28, or only on the top portion of the inner surface 29 of the housing 28. The UV / blue light emitted by the LED chip 22 is mixed with the light emitted by the phosphor layer 34, and the mixed light is transmitted. Of course, the phosphor composition can be located in any two or all three locations (such as Figures 4 to 622) or any other suitable location, such as separate from the housing 28, away from or integrated into the LED chip 22. In one embodiment, the phosphor layer 34 can be a film and away from the LED chip 22. In another embodiment, the phosphor layer 34 can be a film and disposed on the LED chip 22. In some embodiments, the phosphor layer 34 can be applied to the LED chip 22 as an ink composition. In some embodiments, the phosphor layer 34 can be applied to the LED chip 22 as an ink composition and dried to form a film on the LED chip 22. In some embodiments, the phosphor composition can be a single layer or multiple layers. In some embodiments, the film is a multilayer structure, wherein each layer of the multilayer structure includes at least one phosphor or quantum dot material. In another embodiment, the device structure includes a phosphor composition layer on the LED chip and a remote layer including a quantum dot material. In another embodiment, the device structure includes a phosphor composition layer on the LED chip and a remote layer including a quantum dot material and a phosphor material. In another embodiment, the device structure includes a phosphor composition layer on the LED chip and a film including a quantum dot material positioned away from the LED chip. In another embodiment, a device structure includes a layer of a phosphor composition on an LED chip and a film including a quantum dot material and a phosphor material located remote from the LED chip.
[0135] In any of the above structures, the lighting device 20 (FIG. 1 to FIG. Figure 4 ) may also include a plurality of scattering particles (not shown) embedded in the encapsulant material 32. The scattering particles may include, for example, aluminum oxide, silicon dioxide, zirconium oxide, or titanium dioxide. The scattering particles effectively scatter the directional light emitted from the LED chip 22, preferably with negligible absorption.
[0136] In one embodiment, Figure 3 or Figure 4 The lighting device 20 shown may be a backlight device. In another embodiment, the backlight device includes a backlight unit 10. Some embodiments include a surface mounted device (SMD) type light emitting diode 50 for backlight applications, such as Figure 5A , Figure 5B and Figure 5C See Figure 5A , the SMD is of "side emission type" and has a light emitting window 52 on a protruding portion of a light guide member 54. The SMD package comprises an LED chip 56 as defined above and a phosphor composition 58 as described herein. Figure 5B A phosphor composition 58 is shown disposed on an LED chip 56. Figure 5C A phosphor composition 58 is shown disposed remotely from the LED chip 56 . Figure 5B and Figure 5CAlso shown are LED chips 56 and light guide members 54 disposed on a reflective layer 59. The reflective layer 59 reflects light from the LED chips 56 and the light guide members 54 to the phosphor composition 58. The reflective layer 59 can be any material suitable for reflecting light. In one embodiment, the reflective layer 59 can be a metal layer, such as silver, aluminum, an aluminum alloy, or a silver alloy. In another embodiment, the device can be a direct-illuminated display.
[0137] By using the phosphor compositions described herein, a device for generating white light for display applications, such as an LCD backlight unit, can be provided, which has a high color gamut and high luminance. Alternatively, a device for generating white light can be provided for general lighting with high luminance and high CRI values for a wide range of color temperatures of interest (2000K to 10,000K).
[0138] The device of the present disclosure includes lighting and display equipment for general lighting and display applications. The example of display equipment includes liquid crystal display (LCD) backlight unit, TV, computer monitor, vehicle display, laptop computer, computer notebook, mobile phone, smart phone, tablet computer and other handheld devices. In the case where the display is a backlight unit, the phosphor composition can be incorporated into a film, sheet or strip that is coupled to the LED light source for radiation coupling and / or optical coupling, as described in U.S. Patent Application Publication No. 2017 / 0254943. The example of other devices includes colored lamps, plasma screens, xenon excitation lamps, UV excitation marking systems, car headlights, home and theater projectors, laser pumping devices and point sensors. In one embodiment, the device can be a fast response display that does not include LCD. The fast response display can be a self-emitting display including phosphor conversion (PC) micro-LED. The list of these applications is merely intended to be exemplary rather than exhaustive.
[0139] In some embodiments, the film including the phosphor composition can be disposed on a small size LED, such as a micro LED or a mini LED. In other embodiments, the film includes a phosphor having a micron or submicron particle size. In other embodiments, the film includes nanometer-sized particles. In one embodiment, the film includes Mn 4+Doped phosphors having a D50 particle size of less than 20 μm, less than 10 μm, particularly less than 5 μm, and more particularly nanometer-sized. In another embodiment, the D50 particle size may be from about 1 micron to about 20 microns. In another embodiment, the D50 particle size is from about 1 micron to about 15 microns. In another embodiment, the D50 particle size is from about 1 micron to about 10 microns. In another embodiment, the D50 particle size is from about 1 micron to about 5 microns. In another embodiment, the D50 particle size is from about 1 micron to about 3 microns. In another embodiment, the D50 particle size is from about 50nm to about 1000nm. In another embodiment, the D50 particle size is from about 100nm to about 1000nm. In another embodiment, the D50 particle size is from about 200nm to about 1000nm. In another embodiment, the D50 particle size is from about 250nm to about 1000nm. In another embodiment, the D50 particle size is from about 500nm to about 1000nm. In another embodiment, the D50 particle size is from about 750nm to about 1000nm. In another embodiment, the D50 particle size is from about 50nm to about 10 microns. In another embodiment, the D50 particle size is from about 200nm to about 5 microns. In another embodiment, the D50 particle size is from about 250nm to about 5 microns. In another embodiment, the D50 particle size is from about 500nm to about 5 microns. In another embodiment, the D50 particle size is from about 750nm to about 5 microns. In another embodiment, the D50 particle size is from about 750nm to about 3 microns.
[0140] Figure 6 is a schematic diagram of a contact stencil printing system 100 according to one embodiment of the present disclosure. The contact stencil printing system 100 can be used to deposit a composition, such as a phosphor ink, onto a target substrate comprising a plurality of light emitting elements, including but not limited to LEDs, mini-LEDs, OLEDs, or micro-LEDs.
[0141] The contact stencil printing system 100 may include a substrate 102, a substrate support 104, a stencil 106, a stencil frame fixture 108, and an alignment adjuster 112. The stencil 106 may be fabricated on flexible 2 mil, 3 mil, and 5 mil polyimide substrates. These thicknesses are provided as examples only, and various other thicknesses may be used. In some embodiments, the stencil 106 is made of or Fabrication of polyimide substrates.
[0142] Template 106 includes one or more openings. The one or more openings may include various shapes (e.g., circular, rectangular, square, or any other shape) with a width and / or length as small as 25 μm in size. The one or more openings may be made by a laser cutting tool and may include various patterns, lengths, widths, and orientations. For example, the configuration of the one or more openings may take into account parameters of the composition being deposited, including but not limited to the viscosity, wettability, solvent type, quantity, epoxy / emulsion type, and / or PFS to YAG ratio of the composition.
[0143] The template 106 may be held in place by a plurality of template frame clamps 108. The template 106 is placed on a substrate 102, which is supported by a plurality of supports 104. The substrate 102 and the supports 104 may be located on an adjustable surface 110. The adjustable surface 110 may be adjusted in a vertical direction via an alignment adjuster 112. More specifically, the alignment adjuster may be configured to adjust the position of the substrate 102 relative to the template 106 so that the template 106 is in contact with the substrate 102.
[0144] In some embodiments, transfer of a composition using stencil printing system 100 occurs as a result of movement of squeegee 120 over stencil 106 while squeegee 120 is pressed down on stencil 106, thereby bringing stencil 106 into contact with substrate 102. Printing speed (e.g., pressing movement over the stencil) is important because slower printing results in more and / or more extensive material transfer because the stencil remains in contact with the substrate longer, while faster printing speeds result in more controlled material transfer due to the small time period interaction between the substrate and stencil.
[0145] Figure 7 is a schematic diagram of a screen-gap stencil printing system 200 according to one embodiment of the present disclosure. The screen-gap stencil printing system 200 can be used to deposit a composition (such as a phosphor ink) onto a target substrate (such as an LED, mini-LED, OLED, or micro-LED). The stencil 106 can be manufactured on flexible 2 mil, 3 mil, and 5 mil polyimide substrates. These thicknesses are provided as examples only, and various other thicknesses can be used. In some embodiments, the stencil 106 is made of or Fabrication of polyimide substrates.
[0146] Template 106 includes one or more openings. The one or more openings may include various shapes (e.g., circular, rectangular, square, or any other shape) with a width and / or length as small as 25 μm in size. The one or more openings may be made by a laser cutting tool and may include various patterns, lengths, widths, and orientations. The configuration of the one or more openings may take into account parameters of the composition being deposited, including but not limited to the viscosity, wettability, solvent type, quantity, epoxy / emulsion type, and / or PFS to YAG ratio of the composition.
[0147] Similar to the contact stencil printing system 100, the screen pitch stencil printing system 200 may include a substrate 102, a substrate support 104, a stencil 106, a stencil frame fixture 108, and an alignment adjuster 112. The stencil 106 may be held in place by a plurality of stencil frame fixtures 108. The stencil 106 is placed on the substrate 102, which is supported by a plurality of supports 104. The substrate 102 and the supports 104 may be located on an adjustable surface 110. The adjustable surface 110 may be adjusted in a vertical direction via the alignment adjuster 112. More specifically, the alignment adjuster may be configured to adjust the position of the substrate 102 relative to the stencil 106 so that the stencil 106 is in contact with the substrate 102. Printing speed (e.g., the extrusion movement on the stencil) is important because slow printing results in more and / or more extensive material transfer because the stencil remains in contact with the substrate for a longer time, while faster printing speeds result in more controlled material transfer due to the small time period interaction between the substrate and the stencil.
[0148] However, the printing system 200 also includes one or more screen spacing or spacers 130. The spacers 130 are located between the substrate 102 and the template 106, thereby separating the substrate 102 and the template 106 by a certain distance. Generally speaking, the farther the spacers 130 are from the substrate 110, the smaller the difference between the contact angles between the template openings and the substrate 110, thereby enabling better printing uniformity over a large printing area. Composition transfer using the template printing system 200 also occurs as a result of the squeegee 120 moving over the template 106 while the squeegee 120 is pressed down on the template 106, thereby bringing the template 106 into contact with the substrate 102.
[0149] In an exemplary embodiment, the template 106 is stretched uniformly on the substrate 102. In some embodiments, the template 106 is cut shorter than the frame stretch limit of the template. Cutting the template 106 shorter than the template frame stretch limit helps to eliminate protrusions that may cause uneven printing. For example, in some embodiments, the template 106 is stretched to the upper limit of the template frame fixture 108. This may cause the template 106 to be stretched uniformly over the entire template area without any protrusions, which will cause uneven printing. In some embodiments, an adhesive such as a tape is attached to one or more edges of the template 106 so that the template 102 is further stretched, thereby removing any unnecessary protrusions and / or ripples in the template. In some embodiments, the adhesive comprises a polyamide tape.
[0150] In some embodiments, calibration is performed before the composition is transferred. More specifically, the spacer 130 introduces a mismatch between the stencil opening and the target printing point. The calibration ensures proper alignment between the stencil opening and the target printing point.
[0151] In some embodiments, multi-pass printing can be used to build printed ink height and / or increase the aspect ratio on the target printing area. Although the spacers 130 of the screen-spacing stencil printing system 200 provide controlled and precise transfer of ink, non-screen-spacing printing (e.g., printing using the contact stencil printing system 100) results in high volume ink transfer. In some embodiments, non-screen-spacing printing (e.g., printing using the contact stencil printing system 100) can be used after screen-spacing printing (e.g., printing using the screen-spacing stencil printing system 200) to build material height and / or increase the aspect ratio on the target printing area. Screen-spacing printing can transfer a controlled amount of ink to build an ink base, on which non-screen-spacing printing can be used to transfer more material. Using the same material base provides better wettability for subsequent printing runs, resulting in better ink transfer and higher height.
[0152] FIG. 8A to FIG. 8C is a schematic diagram of a bank arrangement 200 according to an embodiment of the present disclosure. More specifically, Fig.10 A to Fig.10C shows a bank arrangement 200 at different stages of a dispensing or printing process. Printing and transferring high aspect ratio conversion layers on small feature light emitting elements (e.g., mini-LEDs and / or micro-LEDs) assembled on a flat substrate surface are challenging. The bank arrangement 200 enables high aspect ratio conversion layers to be achieved on small feature light emitting elements in a more efficient and cost-effective manner than current printing and / or dispensing techniques. For example, in some embodiments, an aspect ratio of at least 0.1 (i.e., 1:10) can be achieved. In another embodiment, the aspect ratio is from about 0.1 to about 10. In another embodiment, the aspect ratio is from about 0.1 to 5. In another embodiment, the aspect ratio is from about 0.5 to 5. In another embodiment, the aspect ratio is from about 0.1 to 3, more specifically, 0.1 to 1 and 0.1 to 0.5.
[0153] exist Fig. 8A In the embodiment of the present invention, a plurality of light emitting elements 202 (eg, LEDs, mini-LEDs and / or micro-LEDs) operating at a desired color point (eg, white light) are disposed on a substrate 210. Figure 8B In the embodiment, one or more walls 204 are disposed around each of the plurality of light emitting elements 202. In some embodiments, each light emitting element 202 is surrounded by a continuous wall 204. For example, each light emitting element 202 is surrounded by a plurality of walls 204 forming a closed square, rectangle, or other shape, thereby forming a bank structure surrounding each light emitting element 202. FIG. 8A to FIG. 8D In the embodiment shown, each light emitting element 202 is surrounded by four walls 204 formed on the planar structure 210, and the four walls form a bank structure 206. In other embodiments, such as Fig. 9 , the wall 204 is formed in a layer 244 located on top of a planar substrate 210, thereby forming a well structure 246. Thus, the combined device 200 may include each light emitting element 202 surrounded by a bank structure 206 or a well structure 246. In some embodiments, the bank structure 206 or the well structure 246 is formed via printing (e.g., using Figure 6 Contact stencil printing system 100 or Figure 7 Screen pitch template printing system 200). In other embodiments, screen pitch printing is desired because it provides control over printing speed and having the appropriate opening size can result in the correct amount of material at the desired location being transferred to fill the well structure without any overflow to the next pixel / color filter. In addition, in some embodiments including well structures, a relatively thin template thickness can be used for better perspective to help alignment on a micrometer scale.
[0154] In some embodiments, the walls 204 are made of a reflective material and can therefore act as a reflector. More specifically, the walls 204 are coated with a white surface that reflects back all visible wavelengths that impinge upon them. The reflective material in the walls 204 can increase the brightness of the light-emitting element. In some embodiments, one or more walls 204 are made of a translucent material. For example, in a transparent display application, the walls 204 can be made of a translucent material.
[0155] exist Figure 8C In some embodiments, the bank structure or well structure is filled with an optically active material 230. The optically active material may include a down-conversion material, such as a phosphor material. In some embodiments, the bank structure, or alternatively the well structure, is filled by a dispensing and / or printing method. For example, in some embodiments, the bank structure is filled with an optically active material 230. Figure 6 Contact stencil printing system 100 or Figure 7 The screen spacing template printing system 200 is used to fill the bank structure or well structure. The screen spacing template printing system 200 can transfer materials with high reproducibility and uniformity in a cost-effective manner. In other embodiments, the wells are filled by dispensing or printing methods known in the art.
[0156] Fig.10 is a composition deposited on a substrate 300 using a contact stencil printing system 100, Fig.11 is a composition deposited on substrate 400 using screen-gap stencil printing system 200. Fig.10 and Fig.11 In the embodiment of the present invention, a 3 mil template with a 120 μm square opening and a 450 μm spacing is used. Compared with the contact stencil printing system 100, the screen spacing stencil printing system 200 is able to transfer a larger amount of composition to the surface of the substrate 102. More specifically, the distance between the substrate 102 and the template 106 introduced by the spacer 130 helps to remove the template opening after the composition has been transferred, thereby resulting in a limited composition transfer. This may result in a high aspect ratio (height to width) of the substrate. Since a relatively high height is required to convert blue light emitted from a blue light source such as an OLED, LED, mini-LED or micro-LED or a possible UV light source into red light, a high aspect ratio is desired.
[0157] Fig. 12A and Fig. 12B Included is a graph showing the aspect ratio of a printed ink composition pattern deposited using screen pitch stencil printing. More specifically, Fig. 12A 5 is a three-dimensional graph 500 showing the height 506 and depth 506 of each of the ink compositions deposited along the width 504 of the substrate. Similarly, Fig. 12B The height 512 of each of the ink compositions deposited along the width 514 of the substrate is shown. Fig. 12A and Fig. 12B In the collection, relatively high aspect ratios can be achieved in a reproducible manner using screen-pitch stencil printing. Fig. 12A In the example shown, an aspect ratio of 0.1 is achieved. In another embodiment, the aspect ratio is about 0.1 to about 10. In another embodiment, the aspect ratio is about 0.1 to 5. In another embodiment, the aspect ratio is about 0.5 to 5. In another embodiment, the aspect ratio is about 0.1 to 3, more specifically, 0.1 to 1 and 0.1 to 0.5.
[0158] Fig.13A shows a printed ink composition pattern 600 deposited via screen pitch stencil printing using a 2 mil stencil, and Fig. 13B is a graph 610 of the photoluminescence intensity of pattern 600 under light excitation at 457 nm and emission intensity at 630 nm. Fig.13A and Fig. 13B As clearly illustrated in , screen-spacing stencil printing deposits the ink composition only where it is intended and does not cause any overflow.
[0159] Fig.14A and Fig. 14B is a schematic diagram of a high-precision pick and place system 700 according to an embodiment of the present disclosure. More specifically, Fig.14A and Fig. 14B A pick and place arrangement 700 is shown at various stages of a high precision and high resolution pick and place process. Fig.14A and Fig. 14B The process shown can be used to assemble previously assembled LED panels and individual LEDs.
[0160] exist Fig.14A In the embodiment, the light emitting element 702 is disposed on a substrate. Fig.14A The light emitting surface 704 of each light emitting element 702 is shown prepared. More specifically, each light emitting surface 704 is coated with an optical adhesive 730. Fig.14A In the illustrated embodiment, the optical adhesive 730 is disposed on the emitting surface 704 via spraying using the nozzle 706. However, the optical adhesive 730 may be disposed on the emitting surface 704 via dispensing or other methods known in the art.
[0161] Fig. 14B An optically active film 730 (e.g., a film containing a phosphor material) is shown deposited on each emitting surface 704 coated with an optical adhesive 730. The size and shape of the optically active film 730 can be designed for the emitting surface 704. For example, prior to assembly, a large area of optically active film can be cut into small area pieces via a laser, a sharp roll cutter, or other methods known in the art. Fig. 14BIn the illustrated embodiment, the optically active film 730 is disposed on the emitting surface 704 coated with the optical adhesive 730 via a high precision pick and place tool 740. In some embodiments, the pick and place tool 740 includes a suction nozzle configured to pick up the optically active film 730 and place the optically active film 730 on the emitting surface 704. The optical adhesive 730 secures the optically active film 730 to the emitting surface 704. In some embodiments, the optically active film 730 is cured using hot air, UV light, and / or any other method known in the art. The optically active film 730 enables the light emitting element 702 to operate at a desired color point (e.g., white light).
[0162] Fig.15 is a dip coating system 900 according to an embodiment of the present disclosure. Similar to the high precision pick and place system 700, the dip coating system 900 uses a high precision pick and place tool 940. However, the dip coating system 900 uses a pick and place tool 940 to pick up each light emitting element 902 and immerse each light emitting element 902 in an ink composition 950. In some embodiments, the pick and place tool 940 includes a suction nozzle configured to pick up the light emitting element 902 and immerse the light emitting surface of the light emitting element 902 in an ink composition bath 950. The immersion time, surface wettability, and bath temperature will define the volume transfer. The ink composition 950 may include a phosphor material. In some embodiments, the ink composition 950 includes a PFS phosphor and / or a KFS phosphor. Additionally or alternatively, the ink composition 950 includes an optical adhesive. The ink composition 950 may include any of the ink compositions described herein.
[0163] After the target immersion time, the pick and place tool 940 removes the light emitting element 902 from the ink composition bath 950. The resulting coating 906 on the light emitting element 902 is then cured. In some embodiments, hot air and / or UV light are used to cure the coating 906. Additionally or alternatively, the ink composition can be cured using any method known in the art. Repeat the process (e.g., immersing the light emitting element 902 in the ink composition bath 950 and curing the resulting coating 906) until the desired conversion layer is obtained. The cured coating on the light emitting element 902 enables the light emitting element 902 to operate at a desired color point (e.g., white light). More specifically, LEDs (e.g., small LEDs, micro LEDs, etc.) can be customized to have a desired color point as a component of any desired panel that can be assembled into an electronic assembly line, resulting in a relatively fast, efficient, and cost-effective process.
[0164] Fig.16A is a top view of an example red-green-blue (RGB) pixel 1000 including a blue sub-pixel 1010 , a green sub-pixel 1020 , and a red sub-pixel 1030 . Fig. 16B 1000. Each sub-pixel may include a well including a plurality of walls. An ink composition including a phosphor that emits blue may be deposited in a blue sub-pixel 1010, an ink composition including a phosphor that emits green may be deposited in a green sub-pixel 1022, and an ink composition including a phosphor that emits red may be deposited in a red sub-pixel 1030. The ink compositions deposited into the blue sub-pixel 1012, the green sub-pixel 1020, and the red sub-pixel 1030 may be cured into color filter components 1012, 1022, and 1032, respectively. Thus, the blue sub-pixel 1010 is configured to emit blue light 1016, the green sub-pixel 1020 is configured to emit green light 1026, and the red sub-pixel 1030 is configured to emit red light 1036. In some embodiments, each sub-pixel 1010, 1020, 1030 includes a color filter material 1014, 1024, 1034, respectively. In some embodiments, stencil printing is used to deposit the ink composition. Stencil printing can be performed via a contact stencil printing system 100 (see Figure 6 ) or screen spacing stencil printing system 200 (see Figure 7 The ink composition may be cured using hot air, UV light and / or any other method known in the art.
[0165] In some embodiments, the ink composition may include a refractive index of about 0.1 to about 3. In further embodiments, the ink composition may include a refractive index of about 1 to about 1.6. In further embodiments, the ink composition may include a refractive index of about 1.50. In further embodiments, the ink composition may include a refractive index of about 1.51. Ink compositions including a relatively high refractive index increase the effective path length of the excitation light 1040 (e.g., blue light) for additional absorption.
[0166] In some embodiments, as described above, a scattering agent is added to the sub-pixel. In some embodiments, the scattering agent may comprise a refractive index of about 0.1 to about 3. In other embodiments, the scattering agent may comprise a refractive index of about 1 to about 1.6. In other embodiments, the scattering agent may comprise a refractive index of about 1.50. In other embodiments, the scattering agent may comprise a refractive index of about 1.51. The inclusion of a scattering agent with a relatively high refractive index increases the effective path length of the excitation light 1040 (e.g., blue light) for additional absorption.
[0167] In some embodiments, a sub-pixel may be partially filled with a first ink composition and partially filled with a second ink composition. The second ink composition may be located near a portion of the pixel or sub-pixel into which the excitation light enters (e.g., Fig. 16BThe excitation light 1040 may enter the pixel and encounter the second ink composition and then the first ink composition. A two-pass printing method may be used to fill the sub-pixel. Printing may be performed via a contact stencil printing system 100 (see Figure 6 ) or screen spacing stencil printing system 200 (see Figure 7 ). The ink composition may be cured using hot air, UV light, and / or any other method known in the art. The first ink composition and the second ink composition may comprise different refractive indices. For example, in some embodiments, the second ink composition comprises a relatively low refractive index and the first ink composition comprises a relatively high refractive index. For example, in some embodiments, the first ink composition comprises a higher refractive index than the second ink composition. This causes the excitation light to first encounter the second ink composition, which results in low reflection, and then encounter the first ink composition, which increases the effective excitation light path once coupled into the color filter component. In other embodiments, the second ink composition comprises a refractive index of about 0.1 to about 2. In other embodiments, the second ink composition comprises a refractive index of about 0.1 to about 1.6. In other embodiments, the second ink composition comprises a refractive index of about 0.1 to about 1.51. In some embodiments, the first ink composition comprises a refractive index greater than about 1. In other embodiments, the first ink composition comprises a refractive index greater than about 1.3. In other embodiments, the first ink composition comprises a refractive index greater than about 1.50. In other embodiments, the first ink composition comprises a refractive index greater than about 1.51.
[0168] In some embodiments, in addition to the first ink composition and the second ink composition, the sub-pixel may further include a third ink composition. In such embodiments, the second ink composition has a relatively low refractive index, the first ink composition may have a relatively high refractive index, and the third ink composition may have a relatively high refractive index. In such embodiments, the first ink composition and the third ink composition may each have a higher refractive index than the second ink composition. In further embodiments, the second ink composition comprises a refractive index of about 0.1 to about 2. In further embodiments, the second ink composition comprises a refractive index of about 0.1 to about 1.6. In further embodiments, the second ink composition comprises a refractive index of about 0.1 to about 1.51. In some embodiments, the first ink composition comprises a refractive index greater than about 1. In further embodiments, the first ink composition comprises a refractive index greater than about 1.3. In further embodiments, the first ink composition comprises a refractive index greater than about 1.50. In further embodiments, the first ink composition comprises a refractive index greater than about 1.51. In some embodiments, the third ink composition comprises a refractive index greater than about 1. In further embodiments, the third ink composition comprises a refractive index greater than about 1. In further embodiments, the third ink composition comprises a refractive index greater than about 1.50. In further embodiments, the third ink composition comprises a refractive index greater than about 1.51.
[0169] In some embodiments, at least one film (not shown) is disposed on the side of one or more sub-pixels 1010, 1020, 1030 or on the pixel 1000 through which the excitation light enters (e.g., side 1002). At least one film can be configured to change the optical properties. For example, at least one filter can include a film that transmits blue light and reflects red light and / or green light, thereby increasing the brightness by increasing the amount of blue light that enters the sub-pixels 1010, 1020, and 1030 and passes through the blue sub-pixel 1010 and is converted to green light by the green sub-pixel 1020 and is converted to red light by the red sub-pixel 1030. In some embodiments, at least one filter includes a dichroic filter. Additionally or alternatively, at least one film is configured to protect the ink composition from at least one of oxygen or moisture.
[0170] In some embodiments, quantum dots in color filters (QDCF) are used. QDCF can improve the color quality, viewing angle, and energy efficiency of the display. By using a blue light source or UV light source such as OLED, LED, mini-LED, or micro-LED, and replacing the traditional color filter with QDCF material, at least a portion of the blue light is converted to a higher wavelength range such as red and / or green light.
[0171] In some embodiments, the RGB pixel 1000 is part of a display device that includes a backlight unit (BLU) 1040 configured to emit blue light. In such embodiments, the QDCF may include a scattering agent in the blue sub-pixel 1010 and quantum dots in the red sub-pixel 1030 and the green sub-pixel 1020 to obtain a wide color gamut. In addition to the quantum dots in the red sub-pixel 1030 and the green sub-pixel 1020, at least one binder, at least one scattering agent, and / or additional color filter materials that absorb blue light may be added to minimize blue light leakage through the sub-pixels, which would result in a lower color gamut.
[0172] The nanometer size of quantum dots, high absorption cross-sections, and surface termination of quantum dots with ligands have led to the commercialization of display architectures comprising QDCFs. However, the use of QDCFs has some disadvantages, such as self-absorption losses. In addition, encapsulation of quantum dots is generally required in displays comprising QDCFs to prevent degradation of the quantum dots due to moisture and / or oxygen. Encapsulation may introduce parallax problems. In addition, the necessary coating, shell, printing and / or curing processes may reduce the quantum efficiency of quantum dots in QDCF components. In some cases, the net effect is a reduction in external quantum efficiency due to significant overlap between quantum dot absorption and emission in heavily loaded inks. It was previously believed that typical phosphors could not be used in color filter applications because the particle size was too large, and if synthesized as submicron, the quantum efficiency and absorption would be too low and the agglomeration would be too high to be printed as sub-pixels. The embodiments disclosed herein solve the above-mentioned problems of current QDCFs.
[0173] In some embodiments according to the present disclosure, a stencil-printed ink composition is used to fill the red sub-pixel 1030. In some embodiments, the ink composition comprises a KSF phosphor (K2SiF6: Mn) having a small particle size and a high manganese content. In contrast to quantum dot color filter solutions, the KSF phosphor (K2SiF6: Mn) has a narrower emission intensity, does not have self-absorption problems in thick films, and does not reduce quantum efficiency when cured into a color filter component. In other embodiments, the D50 particle size of the KSF phosphor is from about 0.1 μm to about 15 μm, and comprises at least 2.0 wt% of the Mn content. In other embodiments, the D50 particle size of the KSF phosphor is from about 0.1 μm to about 8 μm, and comprises at least 2.0 wt% of the Mn content. In other embodiments, the D50 particle size of the KSF phosphor is from about 0.1 μm to about 4 μm, and comprises 2.0 to 4.0 wt% of the Mn content. In other embodiments, the ink composition comprises NSF phosphor (Na2SiF6) having a small particle size and a high manganese content. The stencil printing can be performed via a contact stencil printing system 100 (see Figure 6 ) or screen spacing stencil printing system 200 (see Figure 7 The ink composition may be cured using hot air, UV light and / or any other method known in the art.
[0174] In some embodiments, the red sub-pixel 1030 is coated with an ink composition containing a KSF phosphor using stencil printing, as described above. The ink composition may also include a surface agent such as MgF2 to allow a well-dispersed KSF ink with good printability to absorb most of the excitation light (e.g., blue light or UV light) and have a quantum efficiency greater than 80%. Such ink compositions lack self-absorption, have good reliability, and do not require encapsulation. In addition, typical KSF inks require a loading of 30-70% to absorb most of the excitation light in a well with a depth of 8-16 μm. In another embodiment, the green sub-pixel 1020 is coated with a green luminescent material, and a scattering agent or a blue luminescent material is added to the blue sub-pixel 1010. Such embodiments enable a display that functions when excited by blue LED or OLED light or UV light.
[0175] Additionally, in some embodiments, one or more walls of a sub-pixel are coated with a reflective (eg, white) surface. For example, in some embodiments, one or more walls of a red sub-pixel 1030 are coated with a reflective layer (eg, white).
[0176] In some embodiments, the subpixels of the RGB pixel 1000 include a depth of 6-20 μm. In other embodiments, the subpixels of the RGB pixel 1000 include a depth of 14-20 μm. The inventors have found that increasing the well depth from 8 μm to 16 μm increases the red light emission 1036 of the red subpixel 1030 by more than 30% compared to a red subpixel including a well depth of 8 μm.
[0177] Fig.17 1 is a graph 1100 comparing red light emission of color filter components having red sub-pixels filled with KSF phosphor having a depth of 8 μm and a depth of 16 μm. Fig.17 In the embodiment of the present invention, the ink refractive index and viscosity vary between the color filter components, which will be described in more detail below. Fig.17 1 , features 1-9 on the x-axis 1102 correspond to a well depth of 8 μm, while features 10-14 on the x-axis 1104 correspond to a well depth of 16 μm.
[0178] Red light emission was tested using a first method 1108 using an Edinburgh spectrometer and a second method 1110 using a QE tester. In the first method 1108, the coated color filter components were excited by a Xe lamp, selecting 450nm excitation via a monochromator. A series of gratings and mirrors produced a spot size of approximately 2cm, exciting a 60×60mm coated color filter component. Most of the blue light that strikes the red sub-pixel is transmitted into the cured sub-pixel and is attenuated as the KSF phosphor ink absorbs the light, such that less than 20% of the incident blue light needs to be absorbed by the color filter material after passing through the cured KSF phosphor ink. The KSF phosphor ink converts the absorbed blue photons into red photons via down conversion, and the emitted red photons pass through the color filter material and exit the back of the color filter component. These emitted red photons then pass through a second monochromator and are detected by a photomultiplier tube (PMT) detector. The KSF phosphor printed color components are then compared to each other based on the integrated red emission intensity.
[0179] The second method 1110 uses a QE tester that involves a blue LED with a reflective ring. A KSF phosphor coated color filter component is located on top of the ring in a closed integrating sphere, and the emitted red intensity is coupled out of the integrating sphere via an optical fiber coupled to a charge coupled device (CCD) array detector. The integrated red emission intensity of each component can then be compared and normalized to the component with the highest integrated emission intensity. The correlation between the first method 1108 and the second method 1110 is 95.6%, providing confidence in the measurement.
[0180] Fig.17 The color filter element 14 is printed with an ink composition having a refractive index greater than 1.57 and a viscosity of about 5000 cPs. The wells of the color filter element 14 are completely filled as determined by profilometry. Fig.17 As clearly shown, portion 14 produces the greatest brightness. 3-5 micron NSF phosphor printed color filter components were also fabricated and measured, and brightness up to 90% relative to color filter component 14 was achieved.
[0181] Example
[0182] Example 1
[0183] Sample OS042022:
[0184] 2.2167g SFZ-1+0.4545g BB PTh+0.8589g DGME were weighed in a 15ml (4dram) amber bottle. The mixture was shaken on a vortex mixer for 15-20s. The first increment of PFS (1.0007g) was added and the mixture was shaken on a vortex mixer for 20-30s. A second portion of PFS (1.0008g) was added, and the mixture was shaken on a vortex mixer again, followed by 3-5 minute bath sonication. The third amount of PFS (1.0065g) was added, followed by vortex mixing and bath sonication. After the last addition of PFS (0.9956g) and subsequent mixing and sonication, the slurry was too dry and 1.1579g DGME was added, followed by mixing and bath sonication again. The slurry is still viscous, and adds other 0.2476gDGME, then vortex mixes and bath sonication.Then with horn type sonicator, the slurry is subjected to pulse sonication (1s opens, 2s closes), and 20s active sonication is carried out in total. The slurry heats up, but it is still viscous.Add 0.1102g DGME again, then vortex mixes and bath sonication is carried out again.Then with horn type sonicator, the slurry is subjected to pulse sonication (1s opens, 2s closes), and 20s active sonication is carried out in total.Then the slurry is rolled overnight, and with horn type sonicator, it is subjected to pulse sonication (1s opens, 2s closes), and 20s active sonication is carried out in total the next day.Then it is placed in the desiccator under vacuum for 15min, to degas before coating.
[0185] Scrape coating on glass substrates
[0186] The ink was coated on a 1" x 1" Corning glass substrate with a thickness of 1.1 mm using an Erichsen Coatmaster 510 coater with a vacuum stage. To obtain a final film thickness of 10-30 μm, an applicator with a gap of 1-3 mils was used at a speed of 10 mm / s.
[0187] The glass substrates coated with the wet films were placed on a hot plate at 110° C. to remove the solvent, and then they were UV cured for 2 min.
[0188] Table 1
[0189] Membrane ID Gap (mil) Final thickness(um) OS042022-1 mil-A 1 7 OS042022-1 mil-B 1 8 OS042022-1 mil-C 1 11 OS042022-1 mil-D 1 12 OS042022-1 mil-E 1 14 OS042022-1 mil-F 1 15 OS042022-2 mil-A 2 18 OS042022-2 mil-B 2 20 OS042022-2 mil-C 2 22 OS042022-2 mil-D 2 22 OS042022-3 mil-A 3 28 OS042022-3 mil-B 3 28 OS042022-3 mil-C 3 32 OS042022-3 mil-D 3 32
[0190] Sample OS041522:
[0191] 2.218g SFZ-1+0.4562g BB PTh+0.5515gDGME are weighed in 15ml (4dram) amber bottle. The mixture is shaken on a vortex mixer for 15-20s. The PFS (1.0004g) of the first increment is added and the mixture is shaken on a vortex mixer for 20-30s. The second portion of PFS (1.0072g) is added, and the mixture is shaken on a vortex mixer again, followed by 3-5 minute bath sonication. The PFS (1.0122g) of the third amount is added, followed by vortex mixing and 3-5min bath sonication. After the last addition of PFS (0.9768g) and subsequent mixing and 3-5min sonication, the slurry is too dry and viscous and 0.2562gDGME is added, and then mixed and bath sonication are again performed. The slurry is still viscous, and adds another 0.2097g DGME, followed by vortex mixing and 3-5min bath ultrasonic treatment. Then the slurry is subjected to pulse ultrasonic treatment (1s is on, 2s is off) with a horn-type ultrasonic generator, and 1min active ultrasonic treatment is carried out in total. The slurry heats up and thins out. The slurry is then rolled overnight, and the next day, the slurry is subjected to pulse ultrasonic treatment (1s is on, 2s is off) with a horn-type ultrasonic generator, and 1min active ultrasonic treatment is carried out in total, and heats up. It is then placed in a desiccator under vacuum for 15min, to degas before coating.
[0192] Scrape coating on glass substrates
[0193] The ink was coated on a 1" x 1" Corning glass substrate with a thickness of 1.1 mm using an Erichsen Coatmaster 510 coater with a vacuum stage. To obtain a final film thickness of 10-30 μm, an applicator with a gap of 1-3 mils was used at a speed of 10 mm / s.
[0194] The glass substrates coated with the wet films were placed on a hot plate at 110° C. to remove the solvent, and then they were UV cured for 2 min.
[0195] Table 2
[0196] Membrane ID Gap (mil) Film thickness (μm) OS041522-0.5 mil-A 0.5 3 OS041522-0.5 mil-B 0.5 7 OS041522-0.5 mil-C 0.5 5 OS041522-1 mil-A 1 9 OS041522-1 mil-B 1 13 OS041522-1 mil-C 1 12 OS041522-1 mil-D 1 15 OS041522-1 mil-E 1 14 OS041522-1.5 mil-A 1.5 18 OS041522-1.5 mil-B 1.5 22 OS041522-1.5 mil-C 1.5 14 OS041522-1.5 mil-D 1.5 16
[0197] Sample OS031422:
[0198] 3.6793g SFZ-1+0.602g BB PTh+1.0089g DGME were weighed in a 15ml (4dram) amber bottle. The mixture was shaken on a vortex mixer for 15-20s. 6.3621g of PFS (total amount) was added in three batches. After adding each portion, the mixture was shaken on a vortex mixer for 20-30s, and then a 3-5min bath was ultrasonicated. The slurry was then subjected to pulse ultrasonication for 3min (1s on, 2s off) using a horn-type ultrasonic generator, and a 1min active ultrasonication was performed in total. It was then placed in a desiccator under vacuum for 10min, to degas before coating.
[0199] Scrape coating on glass substrates
[0200] The ink was coated on a 1" x 1" Corning glass substrate with a thickness of 1.1 mm using an Erichsen Coatmaster 510 coater with a vacuum stage. To obtain a final film thickness of 10-30 μm, an applicator with a gap of 1-3 mils was used at a speed of 10 mm / s.
[0201] The glass substrates coated with the wet films were placed on a hot plate at 110° C. to remove the solvent, and then they were UV cured for 2 min.
[0202] Table 3
[0203]
[0204] Sample OS031122:
[0205] 4.2766g SFZ-1+0.2354g BB PTh+1.0381g DGME were weighed in a 15ml (4dram) amber vial. The mixture was shaken on a vortex mixer for 15-20s. The first increment of PFS (2.7311g) was added and the mixture was shaken on a vortex mixer for 20-30s. A second portion of PFS (2.3979g) was added and the mixture was shaken on a vortex mixer again. The slurry was too dry. 1.066g DGME was added and the mixture was shaken on a vortex mixer for 20-30s. The third amount of PFS (2.2586g) was added and then vortexed. The slurry was too viscous and 0.4086g DGME was added and then mixed again. The slurry was still viscous and another 0.2176g DGME was added and then vortexed. The slurry was then pulsed sonicated for 3 min (1 s on, 2 s off) using a horn sonicator. The slurry was too thin. 0.4131 g PFS was added followed by vortex mixing. The slurry was then pulsed sonicated for 3 min (1 s on, 2 s off) using a horn sonicator and 3-5 min bath sonication. It was then placed in a desiccator under vacuum for 15 min to degas before coating.
[0206] Scrape coating on glass substrates
[0207] The ink was coated on a 1" x 1" Corning glass substrate with a thickness of 1.1 mm using an Erichsen Coatmaster 510 coater with a vacuum stage. To obtain a final film thickness of 10-30 μm, an applicator with a gap of 1-3 mils was used at a speed of 10 mm / s.
[0208] The glass substrates coated with the wet films were placed on a hot plate at 110° C. to remove the solvent, and then they were UV cured for 2 min.
[0209] Table 4
[0210]
[0211]
[0212] Sample OS031022:
[0213] Weigh 6.1161g SFZ-1+3.0002g PFS in 15ml (4dram) amber bottle.The mixture is shaken on a vortex mixer for 15-20s and subjected to 3-5min bath ultrasonic treatment.Add a portion of PFS (3.0064g) and the mixture is shaken on a vortex mixer for 20-30s.The mixture is too dry.Add 0.5112g DGME and the mixture is shaken on a vortex mixer for 20-30s.Add the third amount of PFS (3.0051g), then vortex mix.The mixture is too dry, and 0.5141gDGME is added, then mixed again.Then the slurry is pulsed ultrasonically treated (1s on, 2s off) with a horn-type ultrasonic generator, and 1min active ultrasonic treatment is carried out.The slurry is too thin.Add 1.0013g PFS, then vortex mix, and the slurry is still too thin. 0.5086 g PFS was added, followed by vortex mixing and 3-5 min bath sonication. The slurry was pulsed sonicated (1 s on, 2 s off) with a horn-type ultrasonic generator for 1 min of active sonication. It was then placed in a desiccator under vacuum for 15 min to degas before coating.
[0214] Scrape coating on glass substrates
[0215] The ink was coated on a 1" x 1" Corning glass substrate with a thickness of 1.1 mm using an Erichsen Coatmaster 510 coater with a vacuum stage. To obtain a final film thickness of 10-30 μm, an applicator with a gap of 1-3 mils was used at a speed of 10 mm / s.
[0216] The glass substrates coated with the wet films were placed on a hot plate at 110° C. to remove the solvent, and then they were UV cured for 2 min.
[0217] Table 5
[0218]
[0219] Example 2
[0220] The following table describes examples of inks containing small-sized, surface-modified phosphor materials developed in the present invention. The ink embodiments listed in this table illustrate the versatility of the present technology in producing fluids with customized viscosities and using solvents with proven printability. In addition, examples are provided of how to use readily available resin systems from different commercial suppliers to obtain stable phosphor dispersions.
[0221] Experimental Procedure for Formulating the Inks in Samples 1-4:
[0222] Use a disposable pipette to add the resin to a glass vial. Add solvent to the resin and vortex for 3 minutes or until the resin is completely dissolved in the solvent. In some embodiments, the solvent is optional. Visually inspect the bottom of the jar at the corner where the resin is difficult to stir. Add YAG in increments of ~2g, vortexing the solution for 1 minute between each powder addition. Add PFS in increments of ~1-2g, vortexing the solution for 1 minute between each powder addition. Ultrasonicate the solution at 25% power for 1 minute with a probe ultrasonic generator in pulse mode (total run time ~3 minutes), 1s on, 2s off. Remove excess solvent in a rotary evaporator at a speed between 100 and 170RPM and a bath temperature of 45°C under a vacuum equivalent to 75 Torr. Ink quality measurements are performed at regular time intervals (e.g., every hour) and stopped when the target viscosity is reached.
[0223] Resin-free, low viscosity ink. Sample ink 6 in the table above consists of a co-solvent mixture of triethylene glycol monomethyl ether (TGME) and diethylene glycol dimethyl ether (DGDE) in a mass ratio of 1:1. Ethyl cellulose (EC-HH, 300Pa-s viscosity) is used as a binder material. Ethyl cellulose is added to the TGME / DGDE co-solvent blend at 1 wt % and mixed with a stirring rod until all the binder is dissolved. Then, PFS equivalent to 8 wt % of the co-solvent / binder blend is added. The suspension is stirred and mixed at room temperature and then vortexed for 2 minutes. After vortex mixing, the suspension is bath-sonicated for 10 min to 1 h to reduce the average agglomerate size. After ultrasonic treatment, the suspension is rolled on a ball mill at 60 rpm for 2 h. The solution is then transferred to an amber glass vial and stirred at 60 ° C for 2 h.
[0224] Table 6
[0225]
[0226] Ink compositions using high viscosity resins, solvents and additives. Ink 4 in the table is an exemplary formulation in which NOA68T is used. This embodiment may contain different types of high viscosity resins, which may be photocurable or thermally curable, and may have a starting viscosity in the range of 10,000 cP to 30,000 cP (centipoise). The amount of solvent added to the ink may be 0% to 50% of the weight of the base resin. The type of solvent may be any of the above-mentioned solvents. In exemplary inks 3 and 4, dimethylformamide (DMF) and acetone are used, respectively. The ink must contain between 5% and 60% PFS phosphor material. The phosphor particle size (d50) may be in the range of 0.5-10 microns. Additives such as scattering agents (e.g., ZrO2) and auxiliary phosphor emitters such as YAG phosphors may be used in amounts ranging from 1% to 60%.
[0227] Ink compositions using medium viscosity resins, solvents and additives. Inks 1 and 2 in the table are exemplary formulations using NOA170 resin. The embodiment may contain different types of medium viscosity resins, which may be photocurable or thermally curable and may have a starting viscosity ranging from 1,000 cP to 10,000 cP. The amount of solvent added to the ink may be 0% to 50% of the weight of the base resin. The type of solvent may be any of the above solvents. In exemplary inks 1 and 2, acetone and DMF are used, respectively. The ink must contain between 5% and 60% PFS phosphor material. The phosphor particle size (d50) may be in the range of 0.5-10 microns. Although exemplary inks 1 and 2 do not contain such molecules, additives such as scattering agents (e.g., ZrO2) and auxiliary phosphor emitters such as YAG phosphors may also be used in the composition in amounts ranging from 1% to 60%.
[0228] Ink compositions using low viscosity resins, solvents, and additives. Ink 5 in the table above is an example of a low viscosity formulation in which SR454 resin is used. This embodiment may contain different types of low viscosity resins, which may be photocurable or thermally curable, and may have a starting viscosity ranging from 10 cP to 1,000 cP. The amount of solvent added to the ink may be 0 to 10% by weight of the base resin. The type of solvent may be any of the above solvents. In exemplary ink 5, no solvent is used. The ink must contain between 5% and 60% PFS phosphor material. The phosphor particle size (d50) may vary between 0.5 and 5 microns. Although exemplary ink 5 does not contain additives, they may be present in amounts ranging from 1% to 60%.
[0229] Fig.18 A graph 1200 showing a photoluminescence mapping of a blank substrate including a blue sub-pixel, a green sub-pixel, and a red sub-pixel is shown. More specifically, the graph 1200 shows the intensity (counts / s) 1204 as a function of wavelength (nm) 1202 of the blank substrate. As shown in the graph 1200, a broad red emission from the red sub-pixel and a broad green emission from the green sub-pixel are observed. Fig.19 A graph 1300 is shown showing the intensity (counts / s) 1304 as a function of wavelength (nm) 1302 of a KSF-filled red sub-pixel. As shown in the graph 1300, strong red emission is observed for KSF red sub-pixels with wavelengths greater than 580 nm, demonstrating that Fig.18 Compared with the blank substrate, the light intensity of the red sub-pixel filled with KSF increases.
[0230] Fig. 20A graph 1400 of external quantum efficiency percentage (EQE) 1404 versus thickness measurement (μm) 1402 in relevant form factors is shown to understand product performance. The EQE 1404 is proportional to the amount of light absorbed at 450nm (LED or OLED) and the internal quantum efficiency. Although high EQE for the thinnest possible film is desirable, as higher thickness is associated with higher self-absorption losses. However, in general, for light-emitting materials, the thinner the film, the lower the EQE. However, the ink formulations and systems and methods for dispensing and printing such ink formulations as described herein result in EQE improvements of 10 to 20%, enabling the use of thinner films.
[0231] A see-through display or transparent display is an electronic display that allows the user to see what is displayed on the screen while still being able to see through it. The main applications of transparent displays are head-up displays, augmented reality systems, digital signage, and general large-scale spatial light modulation. Transparent displays provide many of the advantages of digital signage while allowing viewers to see the scene behind the display by mounting light-emitting devices directly on transparent glass to act as pixels. These see-through devices can eliminate the need for backlights or housings and are often used in applications including retail, corporate displays, museum exhibitions, award / trophy display cases, and head-up displays, including automotive applications. Light sources for transparent displays can include LEDs, OLEDs, small EDSs, and / or micro-LEDs. Generally speaking, arrays of smaller-sized LEDs such as small LEDs or micro-LEDs allow for higher transparency and higher resolution than larger-sized LEDs, and have the potential to be brighter than OLED-based transparent displays. However, generally speaking, when the size of the micro-LED is reduced, the EQE of the micro-LED can also be reduced. A typical display substrate includes a plurality of separate micro-LEDs, OLEDs, small EDSs, and / or micro-LEDs arranged in a pixel group, wherein the pixel group includes a device that emits blue, a device that emits green, and a device that emits red. In an embodiment according to the present disclosure, a pixel group may include multiple blue emitting or UV emitting LEDs, OLEDs, small LEDs and / or micro LEDs, and color conversion techniques are used to create other colors of the display. In many transparent display applications, it is desirable to maximize transparency by using small size LEDs, thin metallization lines, and transparent conductive materials (such as indium tin oxide) instead of metallization lines.
[0232] In some embodiments, the metallization layer may include an electrode layer and optionally a barrier layer, but may include other layers. In some embodiments, the metallization layer has a thickness of approximately 0.1-2 microns. The electrode layer may form an ohmic contact with the GaN micro-LED and may be formed of high work function metals such as Ni, Au, Ag, Pd, and Pt. In some embodiments, the electrode layer may be reflective to light emission. In other embodiments, the electrode layer may be transparent to light emission. In some embodiments, the width of the lateral separation position of the metallization layer is less than or equal to the width of the bottom surface of the micro pn diode array. The metallization layer is typically formed to have a uniform thickness and may be deposited by various suitable methods, such as sputtering, electron beam evaporation, and seed layer coating.
[0233] The use of micro-LEDs with relatively large reflective surfaces and phosphor droplets can produce satisfactory light output with minimal loss of transparency. Transparent displays according to the present disclosure can be at least 50% transparent, and in some cases, at least 60% transparent. In some embodiments, the ink composition may include a relatively high refractive index. In one embodiment, the ink composition includes a KSF phosphor (K2SiF6:Mn 4+ ), which is less than 5 microns in size and has a Mn content of at least 1.5 wt % Mn content. Such KSF phosphors can be mixed with green or yellow emitting phosphors such as (Y,Ga,Lu,Gd,Tb)3Al5O 12 :Ce 3+. . The ink composition may include a refractive index greater than about 1.49 to produce scattering with a KSF phosphor having a refractive index of about 1.4. This increases the effective path length of the blue pump source and in a banked micro-LED structure with more transmission and reflection than absorption, and therefore will have increased red and green emission (lower CCT) and higher light output at a given phosphor loading. This architecture produces a phosphor-converted micro-LED array with a color temperature above CCX>0.2, CCY>0.2. Typical inks contain at least 20% phosphor loading and possibly up to 70% phosphor loading, with the ratio of green phosphor to red phosphor loading typically being at least about 2:1 by weight and up to about 20:1 by weight.
[0234] In some embodiments, the viscosity of the ink composition used may be from about 100 cPs to about 30,000 cPs. In other embodiments, the viscosity of the ink composition may be from 500 cPs to 20,000 cPs. In some embodiments, each of the micro-LEDs is located at a bank structure (e.g., Fig. 9The bank structure 246 shown in FIG. 2 makes it possible to use lower viscosity inks as low as 100 cPs. High quality, uniform printed parts are produced with inks ranging from 500 cPs to 20,000 cPs. The bank structure using lower viscosity inks can produce more uniform phosphor-converted micro-LED arrays after printing through a degassing step before curing.
[0235] In some embodiments, at least one reflective layer is formed around each LED, OLED, mini-LED and / or micro-LED. At least one reflective layer can achieve a higher conversion rate because it increases the probability of higher and / or multiple internal reflections of the light, which increases the travel path of the light in the conversion layer, resulting in a higher conversion rate.
[0236] In some embodiments, at least one reflective layer is formed of a metal having high reflectivity in the visible range (such as Al and Ag) and / or a metal forming a reflective or transparent oxide (such as Al). In some embodiments, at least one reflective layer includes one or more dielectric mirrors and / or dichroic mirrors. The dielectric mirrors and / or dichroic mirrors can be adjusted to reflect specific bands and can effectively reflect narrowband emissions.
[0237] In some embodiments, at least one reflective layer is deposited around each LED, OLED, mini-LED and / or micro-LED via screen / stencil printing (e.g., using contact stencil printing system 100, screen pitch stencil printing system 200, etc.), high resolution masking technology, or inkjet printing. In some embodiments, at least one reflective layer may be deposited at the same step (and by the same deposition technique) as the metallization line of the LED array before the LED is placed, thus avoiding additional steps and reducing process costs. Additionally or alternatively, a scattering agent, such as TiO2 or ZrO2, is added. In other embodiments, the particle size of the scattering agent is about 0.1 μm to about 4 μm.
[0238] Fig.21 is a schematic diagram of a hybrid conductive grid 1500. The hybrid conductive grid 1500 can provide higher reflectivity under and around the micro-LEDs 1502 and higher transparency in the areas between the micro-LEDs 1502. In some embodiments, the hybrid conductive grid 1500 is produced by sputtering indium tin oxide (ITO) 1506 and Ag conductive segments 1504 in an alternating manner to form an interconnected conductive grid with desired properties. The hybrid conductive grid 1500 can enhance the reflective properties of at least one reflective layer discussed herein.
[0239] Fig. 22is a contour plot of the color point of an example LED array including a dielectric mirror. To measure the color point of phosphor deposits in an LED array, a Konica Minolta CS-150 color and brightness meter was used. The color point was measured before (e.g., bare LEDs) and after (e.g., coated LEDs) the phosphor was applied. To make the measurement, the colorimeter must be placed at a certain distance in front of the light emitting surface. A typical color point of a bare LED emitting blue with a peak around 450nm was measured to be CCX=0.1640, CCY=0.0130.
[0240] In the case of a transparent substrate, some of the emitted light can escape through the substrate to the back of the device. This effect can be significant when the phosphor is deposited on a transparent area of the substrate. Measuring the brightness and color point emitted from both sides of the device can help assess how much light is lost through the substrate, as shown in Table 7. More specifically, Table 7 shows that approximately 30% of the light in the example LED array is emitted from the back side of the device (column back) compared to the light emitted from the front side of the LED array including the deposited phosphor (column front), and its color point is shifted further away from the device emitting blue (e.g., bare LEDs). By placing a mirror behind the device, the brightness is returned to the front side, and the overall color point (column reflected to the front side) is shifted proportionally. Fig. 22 is a contour plot using the data from Table 7.
[0241] Table 7
[0242] Bare LED front back Forward reflection Brightness, cd / m2 not applicable 6888 3259 9715 ccx 0.1640 0.2190 0.2653 0.2334 ccy 0.0130 0.1172 0.0680 0.1427
[0243] This written description uses examples to disclose the invention, including the best mode, and also to enable any person skilled in the art to practice the invention, including making and using any devices or systems and performing any incorporated methods. The patentable scope of the invention is defined by the claims, and may include other examples that occur to those skilled in the art. Such other examples are intended to be within the scope of the claims if they have structural elements that do not differ from the literal language of the claims, or if they include equivalent structural elements with insubstantial differences from the literal language of the claims.
Claims
1. An ink composition comprising Mn containing formula 1 4+ The phosphor material of the doped phosphor and at least one binder material or solvent, wherein the Mn 4+ The D50 particle size of the doped phosphor is from about 0.5 microns to about 15 microns, and wherein the viscosity of the ink composition is from greater than 2,000 cP to about 30,000 cP A x [MF y ]:Mn 4+ I wherein A is Li, Na, K, Rb, Cs or a combination thereof; M is Si, Ge, Sn, Ti, Zr, Al, Ga, In, Sc, Y, La, Nb, Ta, Bi, Gd or a combination thereof; x is [MF y ]The absolute value of the charge of the ion; and y is 5, 6 or 7.
2. The ink composition of claim 1, wherein the phosphor material is present in an amount of about 5 wt% to about 70 wt%, based on the weight of the ink composition.
3. The ink composition according to claim 1, wherein the Mn 4+ The doped phosphor is selected from K2[GeF6]:Mn 4+ 、K2[SiF6]:Mn 4+ 、K2[TiF6]:Mn 4+ 、K2[SnF6]:Mn 4+ 、Cs2[TiF6]:Mn 4+ 、Rb2[TiF6]Mn 4+ 、Cs2[SiF6]:Mn 4+ 、Rb2[SiF6]:Mn 4+ 、Na2[SiF6]:Mn 4+ 、Na2[TiF6]:Mn 4+ 、Na2[ZrF6]:Mn 4+ 、K3[ZrF7]:Mn 4+ 、K3[BiF6]、K3[YF6]:Mn 4+ 、K3[LaF6]:Mn 4+ 、K3[GdF6]:Mn 4+ 、K3[NbF7]:Mn 4+ and K3[TaF7]:Mn 4+ .
4. The ink composition according to claim 1, wherein the Mn of formula I 4+ Phosphor is K2SiF6:Mn 4+ or Na2[SiF6]:Mn 4+ .
5. The ink composition according to claim 1, wherein the Mn of formula I 4+ The doped phosphor is coated with a surface coating comprising a metal fluoride.
6. The ink composition according to claim 5, wherein the metal fluoride is MgF2 or CaF2.
7. The ink composition of claim 1, wherein the phosphor material further comprises a rare earth containing garnet phosphor doped with at least one of cerium, B, SiAlON, or quantum dots.
8. The ink composition according to claim 1, wherein the ink composition comprises a binder material and a solvent.
9. The ink composition according to claim 1, wherein the binder material is one or more of epoxy resin, acrylate, methacrylate, vinyl ester and siloxane.
10. The ink composition according to claim 1, further comprising a scattering aid.
11. The ink composition according to claim 10, wherein the scattering aid is ZrO2 or TiO2 nanoparticles.
12. The ink composition according to claim 1, wherein the ink composition further comprises one or more other luminescent materials.
13. The ink composition of claim 12, wherein the luminescent material comprises a quantum dot material.
14. The ink composition of claim 13, wherein the quantum dot material comprises perovskite quantum dots.
15. A device comprising an LED light source optically coupled and / or radiatively connected to a phosphor composition comprising a Mn of Formula 1 4+ doped phosphor, wherein the Mn 4+ The D50 particle size of the doped phosphor is about 0.5 microns to about 15 microns, and wherein the aspect ratio of the phosphor composition coupled to the LED light source is at least 0.1, A x [MF y ]:Mn 4+ I wherein A is Li, Na, K, Rb, Cs or a combination thereof; M is Si, Ge, Sn, Ti, Zr, Al, Ga, In, Sc, Y, La, Nb, Ta, Bi, Gd or a combination thereof; x is [MF y ]The absolute value of the charge of the ion; and y is 5, 6 or 7.
16. The device of claim 15, wherein the LED light source is a UV emitting LED or a blue emitting LED.
17. The device of claim 15, wherein the phosphor material is present in an amount of about 5 wt% to about 70 wt% based on the weight of the ink composition.
18. The device according to claim 15, wherein the Mn 4+ The doped phosphor is selected from K2[SiF6]:Mn 4+ 、K2[TiF6]:Mn 4+ 、K2[SnF6]:Mn 4+ 、Cs2[TiF6]:Mn 4+ 、Rb2[TiF6]Mn 4+ 、K2[GeF6]:Mn 4+ 、Cs2[SiF6]:Mn 4+ 、Rb2[SiF6]:Mn 4+ 、Na2[SiF6]:Mn 4+ 、Na2[TiF6]:Mn 4+ 、Na2[ZrF6]:Mn 4+ 、K3[ZrF7]:Mn 4+ 、K3[BiF6]、K3[YF6]:Mn 4+ 、K3[LaF6]:Mn 4+ 、K3[GdF6]:Mn 4+ 、K3[NbF7]:Mn 4+ and K3[TaF7]:Mn 4+ .
19. The device according to claim 15, wherein the Mn of formula I 4+ Phosphor is K2SiF6:Mn 4+ or Na2[SiF6]:Mn 4+ .
20. The device according to claim 15, wherein the Mn of formula I 4+ The doped phosphor is coated with a surface coating comprising a metal fluoride.
21. The device of claim 20, wherein the metal fluoride is MgF2 or CaF2.
22. The device of claim 15, wherein the phosphor material further comprises a rare earth containing garnet phosphor doped with at least one of Ce, B, SiAlON, or quantum dots.
23. The apparatus of claim 15, wherein the ink composition comprises a binder material and a solvent.
24. The device of claim 23, wherein the binder material is one or more of an epoxy, an acrylate, a methacrylate, a vinyl ester, and a siloxane.
25. The device of claim 15, further comprising a scattering aid.
26. The device of claim 25, wherein the scattering aid is ZrO2 or TiO2 nanoparticles.
27. The device of claim 15, wherein the ink composition further comprises one or more other luminescent materials.
28. The device of claim 27, wherein the light-emitting material comprises a quantum dot material.
29. The device of claim 28, wherein the quantum dot material comprises perovskite quantum dots.
30. A lighting device comprising the apparatus according to claim 15.
31. A backlight device comprising the apparatus according to claim 15.
32. A display device comprising the apparatus according to claim 15.
33. The device of claim 15, wherein the LED light source is a mini-LED or a micro-LED.
34. A television comprising the backlight device according to claim 31.
35. A mobile phone comprising the backlight device according to claim 31.
36. A computer monitor comprising the backlight device according to claim 31.
37. A laptop computer comprising the backlight device according to claim 31.
38. A tablet computer comprising the backlight device according to claim 31.
39. An automotive display comprising the backlight device according to claim 31.
40. The device of claim 15, wherein the device is a self-emissive display.
41. A method for inkjet printing, flexographic printing or microdispensing printing, the method comprising printing an ink composition, wherein the ink composition comprises a low viscosity ink composition, the low viscosity ink composition comprising a Mn containing Formula 1 4+ The phosphor material of the doped phosphor and at least one binder material or solvent, wherein the Mn 4+ The D50 particle size of the doped phosphor is about 0.5 microns to about 5 microns, and wherein the viscosity of the ink composition is about 10 cP to about 1000 cP A x [MF y ]:Mn 4+ I wherein A is Li, Na, K, Rb, Cs or a combination thereof; M is Si, Ge, Sn, Ti, Zr, Al, Ga, In, Sc, Y, La, Nb, Ta, Bi, Gd or a combination thereof; x is [MF y ]The absolute value of the charge of the ion; and y is 5, 6 or 7.
42. A method for screen printing, direct writing printing, aerosol jet printing, gravure printing, flexographic printing or micro-dispensing printing, the method comprising printing an ink composition, wherein the ink composition comprises a medium viscosity ink composition, the medium viscosity ink composition comprising a Mn containing Formula 1 4+ The phosphor material of the doped phosphor and at least one binder material or solvent, wherein the Mn 4+ The D50 particle size of the doped phosphor is about 0.5 microns to about 15 microns, and wherein the viscosity of the ink composition is about 1000 cP to about 10,000 cP A x [MF y ]:Mn 4+ I wherein A is Li, Na, K, Rb, Cs or a combination thereof; M is Si, Ge, Sn, Ti, Zr, Al, Ga, In, Sc, Y, La, Nb, Ta, Bi, Gd or a combination thereof; x is [MF y ]The absolute value of the charge of the ion; and y is 5, 6 or 7.
43. A method for screen printing, direct writing printing or extrusion, the method comprising printing or extruding an ink composition, wherein the ink composition comprises a high viscosity ink composition, the high viscosity ink composition comprising a Mn containing formula 1 4+ The phosphor material of the doped phosphor and at least one binder material or solvent, wherein the Mn 4+ The D50 particle size of the doped phosphor is about 0.5 microns to about 15 microns, and wherein the viscosity of the ink composition is about 10,000 cP to about 30,000 cP A x [MF y ]:Mn 4+ I wherein A is Li, Na, K, Rb, Cs or a combination thereof; M is Si, Ge, Sn, Ti, Zr, Al, Ga, In, Sc, Y, La, Nb, Ta, Bi, Gd or a combination thereof; x is [MF y ]The absolute value of the charge of the ion; and y is 5, 6 or 7.
44. A color filter component comprising a well, a first ink phosphor composition and a second ink phosphor composition, the first ink composition having a high refractive index and the second ink phosphor composition having a low refractive index, wherein the second ink phosphor composition is located near a surface through which excitation light enters, The first ink phosphor composition and the second ink phosphor composition include Mn containing Formula 1 4+ The phosphor material of the doped phosphor and at least one binder material or solvent, wherein the Mn 4+ The D50 particle size of the doped phosphor is about 0.5 microns to about 15 microns, and wherein the viscosity of the ink composition is about 10,000 cP to about 30,000 cP A x [MF y ]:Mn 4+ I wherein A is Li, Na, K, Rb, Cs or a combination thereof; M is Si, Ge, Sn, Ti, Zr, Al, Ga, In, Sc, Y, La, Nb, Ta, Bi, Gd or a combination thereof; x is [MF y ]The absolute value of the charge of the ion; and y is 5, 6 or 7.
45. The color filter component of claim 44, wherein the first ink composition has a refractive index greater than about 1.5 and the second ink composition has a refractive index of about 0.1 to about 1.
5.
46. The color filter component of claim 45, wherein the well has a depth of about 6 μm to about 20 μm.
47. A color filter component as claimed in claim 45, wherein at least one wall of the well is coated with a reflective material.
48. A color filter component according to claim 45, wherein at least a portion of the surface through which the excitation light enters is coated with at least one film, and the at least one film is configured to change the optical properties of the color filter component or improve its reliability.
49. A method comprising depositing a first ink composition into a well of a color filter component, and subsequently depositing a second ink composition into the well of the color filter component, wherein the first ink composition has a high refractive index and the second ink composition has a low refractive index, wherein the second ink composition is located near a surface through which excitation light enters, The first ink phosphor composition and the second ink phosphor composition contain Mn containing Formula 1 4+ The phosphor material of the doped phosphor and at least one binder material or solvent, wherein the Mn 4+ The D50 particle size of the doped phosphor is about 0.5 microns to about 15 microns, and wherein the viscosity of the ink composition is about 10,000 cP to about 30,000 cP x [MF y ]:Mn 4+ I wherein A is Li, Na, K, Rb, Cs or a combination thereof; M is Si, Ge, Sn, Ti, Zr, Al, Ga, In, Sc, Y, La, Nb, Ta, Bi, Gd or a combination thereof; x is [MF y ]The absolute value of the charge of the ion; and y is 5, 6 or 7.
50. The method of claim 4649, wherein the first ink composition has a refractive index greater than about 1.5 and the second ink composition has a refractive index of about 0.1 to about 1.
5.
51. A light emitting array comprising a plurality of micro-LEDs, each micro-LED being enclosed in a bank structure or a well structure, the bank structure or the well structure being configured to contain an ink composition deposited within the bank structure or the well structure, The phosphor ink composition comprises Mn containing Formula 1 4+ The phosphor material of the doped phosphor and at least one binder material or solvent, wherein the Mn 4+ The D50 particle size of the doped phosphor is about 0.5 microns to about 15 microns, and wherein the viscosity of the ink composition is about 10,000 cP to about 30,000 cP A x [MF y ]:Mn 4+ I wherein A is Li, Na, K, Rb, Cs or a combination thereof; M is Si, Ge, Sn, Ti, Zr, Al, Ga, In, Sc, Y, La, Nb, Ta, Bi, Gd or a combination thereof; x is [MF y ]The absolute value of the charge of the ion; and y is 5, 6 or 7.
52. A transparent display comprising a micro-LED array coated with a phosphor composition, wherein the transparency of the transparent display is at least 50%, and the phosphor ink composition comprises Mn of Formula 1 4+ doped phosphor, wherein the Mn 4 + The doped phosphor has a D50 particle size of about 0.5 microns to about 15 microns, and wherein the phosphor composition has an aspect ratio of at least 0.1, A x [MF y ]:Mn 4+ I wherein A is Li, Na, K, Rb, Cs or a combination thereof; M is Si, Ge, Sn, Ti, Zr, Al, Ga, In, Sc, Y, La, Nb, Ta, Bi, Gd or a combination thereof; x is [MF y ]The absolute value of the charge of the ion; and y is 5, 6 or 7.
53. The transparent display of claim 52, wherein each micro-LED of the micro-LED array is encapsulated in a bank structure or a well structure.
54. The transparent display of claim 52, wherein the phosphor binder composition further comprises a quantum dot material.
55. An automotive display comprising the transparent display according to claim 52.
56. A television comprising the display device according to claim 32.
57. A mobile phone comprising the display device according to claim 32.
58. A computer monitor comprising the display device according to claim 32.
59. A laptop computer comprising the display device according to claim 32.
60. A tablet computer comprising the display device according to claim 32.
61. An automotive display comprising the display device according to claim 32.
Citation Information
Patent Citations
Films with narrow band emission phosphor materials
US11254864B2
Color stable red-emitting phosphors
US20160244663A1
Devices containing a remote phosphor package with red line emitting phosphors and green emitting quantum dots
US20170254943A1
Processes for preparing color stable red-emitting phosphor particles having small particle size
US20180163126A1
Method to enhance phosphor robustness and dispersability and resulting phosphors
US20200369956A1